Hollow silica sol containing monovalent alkali metal ions and method for producing same

By adding an appropriate amount of sodium ions to the hollow silica particle sol and adjusting its molar ratio, the problem of reduced stability at high temperatures is solved, and the particle size change is reduced and the membrane transparency is improved.

CN119894824AActive Publication Date: 2025-04-25NISSAN CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202480004044.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-07-26
Publication Date
2025-04-25
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

The stability of existing hollow silica particle sols decreases when stored at high temperatures, resulting in large changes in particle size, affecting the transparency and surface quality of the coating.

Method used

By adding 1000 alkali metal ions, especially sodium ions, to the hollow silica particle sol, the molar ratio is adjusted within the range of 7.12×10-6 to 285×10-6, and stored at 50°C for 48 hours, the particle size value of the dynamic light scattering method is determined to be within a range of less than 2.0 times.

Benefits of technology

The stability of the hollow silica particle sol is improved, the particle size changes are reduced, and the transparency and surface quality of the film are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005314791130000111
    Figure BDA0005314791130000111
  • Figure BDA0005314791130000121
    Figure BDA0005314791130000121
  • Figure BDA0005314791130000131
    Figure BDA0005314791130000131
Patent Text Reader

Abstract

The present invention relates to an aqueous sol containing hollow silica particles having high stability and an organic solvent sol, and further relates to a method for improving the stability of the sol having reduced storage stability, and a method for producing the sol. To this end, provided is a hollow silica sol containing hollow silica particles having a space in the interior of an outer shell and monovalent alkali metal ions, the hollow silica particles and the monovalent alkali metal ions are contained such that the number of moles of the monovalent alkali metal ions in terms of M2O (M represents a monovalent alkali metal atom) relative to the number of moles of SiO2 in the hollow silica particles is 7.12 * 10 <-6 > to 285 * 10 <-6 >, and the average particle diameter of the sol measured by dynamic light scattering after being stored at 50 DEG C for 48 hours is greater than or equal to the average particle diameter measured by dynamic light scattering. And the average particle diameter is within 2.0 times the average particle diameter measured by a dynamic light scattering method before storage. And the average particle size measured by a dynamic light scattering method is 20-150nm. A stabilization method in which monovalent alkali metal ions are added to a hollow silica sol having a dynamic light scattering method particle diameter value that has been increased than at the time of production in such a manner that the monovalent alkali metal ions are at the aforementioned ratio with respect to SiO2 of hollow silica particles in the hollow silica sol, thereby reducing the increased dynamic light scattering method particle diameter value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sol in which hollow silica particles containing monovalent alkali metal ions such as sodium ions are dispersed in water or an organic solvent, a method for producing the sol, and a film-forming composition. Background Art

[0002] Hollow silica particles having a silica shell and a space inside the shell have characteristics such as low refractive index, low thermal conductivity (insulation), and electrical insulation.

[0003] The hollow silica particles are composed of a core corresponding to a hollow portion and a shell forming the outer side of the core. An aqueous dispersion of the hollow silica particles is obtained by forming a silica layer on the outer side of the core in an aqueous medium and then removing the core.

[0004] A silicon dioxide-based fine particle having a cavity inside the shell has been disclosed, characterized in that the average particle size is in the range of 5 to 500 nm, the refractive index is in the range of 1.15 to 1.38, and the silicon dioxide is replaced by SiO 2 Inorganic oxides other than silicon dioxide are treated with MO X The molar ratio MO X / SiO 2 The content of alkali metal oxide is in the range of 0.0001 to 0.2. 2 O (A: alkali metal element) is 5 ppm or less (see Patent Document 1).

[0005] Also disclosed is a silica-based fine particle having a porous substance and / or voids inside an outer shell layer, characterized in that a ratio (SB / SC) of a specific surface area (SB) of the fine particle measured by a BET method to a specific surface area (SC) represented by the following formula is in the range of 1.1 to 5, a refractive index is in the range of 1.15 to 1.38, and a content of an alkali metal oxide is expressed as M 2 O (M: alkali metal element) is 5 ppm or less based on the silica-based fine particles, and the content of ammonia and / or ammonium ions is converted to NH 3 The content of the silica-based fine particles is 1500 ppm or less (see Patent Document 2).

[0006] SC(m 2 / g)=6000 / Dp(nm)·ρ

[0007] (Wherein, Dp: average particle size of silica-based fine particles (nm), ρ: density (g / ml).)

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-046606

[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2013-121911 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The present invention relates to an aqueous sol and an organic solvent sol containing highly stable hollow silica particles, and further relates to a method for improving the stability of the sol having reduced storage stability and a method for producing the same.

[0014] Solution

[0015] The present invention, as a first aspect, is a hollow silica sol comprising hollow silica particles having a space inside an outer shell and monovalent alkali metal ions.

[0016] The monovalent alkali metal ion is converted into M 2 O relative to the molar number of SiO 2 The number of moles is 7.12×10 -6 ~285×10 -6 The hollow silica particles and the monovalent alkali metal ions are contained in a ratio of , wherein M represents a monovalent alkali metal atom,

[0017] The average particle size measured by a dynamic light scattering method after the sol was stored at 50° C. for 48 hours was within 2.0 times the average particle size measured by a dynamic light scattering method before the storage.

[0018] Or it is a hollow silica sol, comprising hollow silica particles having a space inside the shell and a monovalent alkali metal ion, wherein the monovalent alkali metal ion is converted into M 2 O relative to the SiO 2 The molar ratio is 7.12×10 -6 ~285×10 -6 The hollow silica particles and the monovalent alkali metal ions are contained in a ratio of , wherein M represents a monovalent alkali metal atom, and the particle size value of the sol after storage at 50° C. for 48 hours is within 2.0 times that before storage.

[0019] As a second aspect, in the hollow silica sol according to the first aspect, the monovalent alkali metal ions are sodium ions.

[0020] As a third aspect, the hollow silica sol according to the first or second aspect has an average particle size of 20 to 150 nm as measured by a dynamic light scattering method.

[0021] As a fourth aspect, the hollow silica sol according to any one of aspects 1 to 3 further contains an amine, wherein the ratio of the amine to SiO2 in the hollow silica particles is 2 It is 0.001 to 10% by mass.

[0022] As a fifth aspect, in the hollow silica sol according to the fourth aspect, the amine is at least one amine selected from primary amines, secondary amines and tertiary amines having 1 to 10 carbon atoms.

[0023] As a sixth aspect, in the hollow silica sol according to the fourth or fifth aspect, the amine is a water-soluble amine having a water solubility of 80 g / L or more.

[0024] Aspect 7 is the hollow silica sol according to any one of aspects 1 to 6, wherein the hollow silica particles further contain aluminum atoms forming aluminosilicate sites, the aluminum atoms are bonded to the surface of the hollow silica particles, and the SiO 2 The mass of the aluminum atom is Al 2 O 3 The conversion ratio A is in the range of 100 to 20,000 ppm, and the aluminum atomic mass is the value measured by the leaching method.

[0025] Alternatively, the hollow silica sol according to any one of aspects 1 to 6, wherein the hollow silica particles contain aluminum atoms forming aluminosilicate sites, wherein the aluminum atoms measured by the leaching method are Al 2 O 3 Calculated relative to 1g SiO 2 The ratio is 100 to 20,000 ppm A, and the aluminum atomic mass is bound to the surface of the hollow silica particles.

[0026] As an aspect 8, the hollow silica sol according to aspect 7, wherein in the measurement of the leaching method for leaching aluminum atoms from a compound containing aluminum atoms bonded to the surface of the hollow silica particles, an aqueous solution of at least one inorganic acid selected from sulfuric acid, nitric acid and hydrochloric acid is used,

[0027] Alternatively, in the hollow silica sol as described in viewpoint 7, in the leaching method, the hollow silica particles are leached with an aqueous solution of at least one inorganic acid selected from sulfuric acid, nitric acid and hydrochloric acid, and the compound containing aluminum atoms bonded to the surface of the hollow silica particles is measured as Al 2 O 3 Calculated relative to 1g SiO 2 The ratio A.

[0028] As a ninth aspect, in the hollow silica sol according to the seventh or eighth aspect, the mass of aluminum atoms present in the entire hollow silica particles is expressed as Al 2 O3 In terms of SiO 2 The mass of the aluminum atom is represented by a ratio B of 120 to 50,000 ppm, the mass of the aluminum atom is a value measured by dissolving the hollow silica particles with a hydrofluoric acid aqueous solution, and the ratio A / the ratio B is 0.002 to 1.0,

[0029] Alternatively, the hollow silica sol according to claim 7 or 8, wherein the aluminum atoms present in the hollow silica particles as a whole are measured by dissolving the hollow silica particles in a hydrofluoric acid aqueous solution, and the aluminum atoms are expressed as Al 2 O 3 Calculated relative to 1g SiO 2 The ratio of A to B is 120 to 50000 ppm, and the A / B is 0.002 to 1.0.

[0030] As aspect 10, the hollow silica sol according to any one of aspects 1 to 9 contains the hollow silica particles having a ratio of [specific surface area C of silica particles obtained by a BET method, i.e., a nitrogen adsorption method] / [specific surface area D of silica particles converted by a transmission electron microscope] of 1.40 to 5.00.

[0031] As an eleventh aspect, in the hollow silica sol according to any one of aspects 1 to 10, the hollow silica particles contain a surface charge amount of SiO 2 Calculated per 1g of hollow silica particles of 5 to 250 μeq / g,

[0032] Or the hollow silica sol according to any one of aspects 1 to 10, comprising SiO 2 Hollow silica particles having a surface charge amount per 1 g of 5 to 250 μeq / g.

[0033] As aspect 12, the hollow silica sol according to any one of aspects 1 to 11, wherein the hollow silica particles further comprise hollow silica particles coated with at least one silane compound selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2),

[0034] R 1 a Si(R 2 ) 4-a Formula (1)

[0035] 〔R 3 b Si(R 4 ) 3-b 〕 2 Y c Formula (2)

[0036] In formula (1),

[0037] R 1 is a group bonded to a silicon atom, and independently represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, a polyether group, a carboxyl group, a protected carboxyl group, a carboxyl generating group, an imide group or a cyano group and bonded to a silicon atom via a Si-C bond, or represents a combination of these groups,

[0038] R 2 is a group or atom bonded to a silicon atom, and each independently represents an alkoxy group, an acyloxy group, a hydroxyl group or a halogen atom having 1 or more carbon atoms, or represents a combination of these groups,

[0039] a represents an integer from 1 to 3,

[0040] In formula (2),

[0041] R 3 is a group bonded to a silicon atom, and independently represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, a polyether group, a carboxyl group, a protected carboxyl group, a carboxyl generating group, an imide group, or a cyano group and bonded to a silicon atom via a Si-C bond, or represents a combination of these groups,

[0042] R 4 is a group or atom bonded to a silicon atom, and each independently represents an alkoxy group, an acyloxy group, a hydroxyl group or a halogen atom having 1 or more carbon atoms, or represents a combination of these groups,

[0043] Y is a group or atom bonded to a silicon atom and represents an alkylene group, an NH group or an oxygen atom,

[0044] b represents an integer of 1 to 3, and c represents an integer of 0 or 1.

[0045] As aspect 13, in the hollow silica sol according to any one of aspects 1 to 12, the dispersion medium is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea or an ester.

[0046] As a fourteenth aspect, a film-forming composition comprises hollow silica particles derived from the hollow silica sol according to any one of aspects 1 to 13, and an organic resin or polysiloxane.

[0047] Aspect 15 is a film obtained from the film-forming composition according to aspect 14 and having a visible light transmittance of 80% or more.

[0048] As aspect 16, there is provided a method for producing a hollow silica sol according to any one of aspects 1 to 13, comprising the following steps (I) to (II):

[0049] (I) Step: a step of preparing a hollow silica sol containing a dispersion medium,

[0050] Step (II): Add monovalent alkali metal ions to the hollow silica sol of step (I) and adjust the amount of monovalent alkali metal ions to M 2 O relative to the molar number of SiO 2 The molar ratio is 7.12×10 -6 ~285×10 -6 wherein M represents a monovalent alkali metal atom.

[0051] As a seventeenth aspect, in the method for producing a hollow silica sol according to the sixteenth aspect, in the step (II), the monovalent alkali metal ion is a sodium ion.

[0052] As aspect 18, in the method for producing a hollow silica sol according to aspect 17, the sodium ion content is adjusted in the step (II) by contacting the hollow silica sol obtained in the step (I) with a cation exchange resin or by adding a sodium source.

[0053] As aspect 19, in the method for producing a hollow silica sol according to aspect 17, in the step (II), the addition of the sodium source is addition of sodium hydroxide.

[0054] As aspect 20, there is provided the method for producing a hollow silica sol according to any one of aspects 16 to 19, wherein the dispersion medium in the step (I) and the step (II) is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea or an ester.

[0055] As aspect 21, the method for producing a hollow silica sol according to any one of aspects 16 to 20, wherein at least one step selected from the following (i) to (iv) is additionally performed in the step (I), the step (II), or both steps.

[0056] (i): Adding amine to the hollow silica sol,

[0057] (ii): sodium aluminate is added as an aluminum source and heated to form aluminosilicate sites in the hollow silica particles,

[0058] (iii): replacing the dispersion medium with another dispersion medium,

[0059] (iv): The hollow silica particles are further coated with at least one silane compound selected from the group consisting of formula (1) and formula (2).

[0060] As a viewpoint 22, the method for stabilizing the hollow silica sol described in the viewpoint 1 is a method for stabilizing the hollow silica sol containing hollow silica particles having a space inside an outer shell, characterized in that the monovalent alkali metal ions are added to the hollow silica sol whose average particle size value measured by a dynamic light scattering method is larger than that during production, so that the monovalent alkali metal ions are converted into M 2 O relative to the molar number of SiO in the hollow silica particles in the hollow silica sol. 2 The number of moles becomes 7.12×10 -6 ~285×10 -6 The molar ratio of , wherein M represents a monovalent alkali metal atom, reduces the increased average particle size measured by dynamic light scattering,

[0061] Alternatively, the method for stabilizing hollow silica sol according to claim 1 is a method for stabilizing hollow silica sol comprising hollow silica particles having a space inside an outer shell, wherein the univalent alkali metal ions are added to the hollow silica sol whose particle size value according to dynamic light scattering method is larger than that during production, so that the univalent alkali metal ions are converted into M 2 O relative to the SiO of the hollow silica particles in the hollow silica sol. 2 The molar ratio becomes 7.12×10 -6 ~285×10 -6 The molar ratio of reduces the increased dynamic light scattering particle size value, wherein M represents a monovalent alkali metal atom.

[0062] As aspect 23, in the method for stabilizing a hollow silica sol according to aspect 22, the monovalent alkali metal ions are sodium ions.

[0063] Effects of the Invention

[0064] Since the dispersion containing hollow silica particles (hollow silica sol) is stable, it is possible to obtain a hollow silica sol in which the hollow silica particles do not aggregate and the hollow silica particle size changes little. When a hollow silica sol with high stability is formed into a film, since the particle size changes little, it is possible to reduce the unevenness of the film surface and improve the transparency.

[0065] The alkali metal ions (e.g., sodium ions) in the hollow silica sol are preferably within a certain range. If the alkali metal ions are too much, the alkali metal ions will be dissolved from the membrane or the electrical insulation of the membrane will cause problems. In addition, if the alkali metal ions are too little, the inside of the shell of the hollow silica particles will become hollow. The specific gravity of the hollow silica particles themselves is lower than that of solid silica particles. Therefore, when the repulsive force between the particles is low, the particles tend to aggregate and condense easily. In this case, a certain amount of alkali metal ions (e.g., sodium ions) is required to increase the repulsive force between the particles.

[0066] In the present invention, the stability is improved by combining amine molecules and sodium ions as the base component. This is considered to be because the bulky amine molecules and sodium ions coexist on the particle surface, further increasing the repulsive force between the silica particles.

[0067] In the present invention, aluminum atoms are doped on the surface of silica particles to form aluminosilicate sites, and the presence of an alkali metal that serves as a counter ion to the negatively charged aluminum atoms can enhance the stabilization of the aluminosilicate sites. DETAILED DESCRIPTION

[0068] The present invention is a hollow silica sol, which contains hollow silica particles having a space inside the shell and monovalent alkali metal ions, wherein the monovalent alkali metal ions are converted into M 2 O (M represents a monovalent alkali metal atom) relative to the molar number of SiO 2 The number of moles is 7.12×10 -6 ~285×10 -6 The sol contains them in a ratio of , and the particle size value (average particle size) by dynamic light scattering after storage at 50° C. for 48 hours is within 2.0 times the particle size value by dynamic light scattering before storage.

[0069] Hollow silica particles have a shell of silica and a space inside the shell. Hollow silica can be obtained by forming a shell mainly composed of silica on the surface of a portion corresponding to a core called a "template" in a dispersion medium and removing the portion corresponding to the core.

[0070] Hollow silica particles are required to be stably dispersed in the dispersion medium, but the presence of silanol groups on the surface of hollow silica particles, the presence of organic functional groups, the presence of aluminosilicate sites formed by doping aluminum atoms, etc., are stabilized by giving monovalent alkali metal ions to the surface of hollow silica particles. There are polymerizable functional groups such as hydroxyl groups in silanol groups, organic functional groups and aminosilicate sites. The interaction between these polymerizable functional groups leads to weak condensation (entanglement) or hydrogen bonds between particles, making the particles cross-linked and the particles unstable or increasing in particle size. However, it can be considered that by adding monovalent alkali metal ions to these polymerizable functional groups, the morphology of hydroxyl groups is changed, and the main cause of instability can be suppressed. These polymerizable functional groups sometimes promote instability by heating. The stability of hollow silica sol can be evaluated by confirming it at 50°C and after 48 hours.

[0071] Examples of the monovalent alkali metal ion include lithium ion, sodium ion, potassium ion, rubidium ion and cesium ion. Preferably, lithium ion, sodium ion and potassium ion are used, and particularly preferably, sodium ion is used.

[0072] The content of the monovalent alkali metal ion is expressed as follows: 2 , convert the monovalent alkali metal ion into M 2 O (wherein M represents a monovalent alkali metal atom) can be 7.12×10 -6 ~285×10 -6 , or 7.12 × 10 -6 ~237×10 -6 , or 7.12 × 10 -6 ~190×10 -6 , or 20×10 -6 ~285×10 -6 , or 50×10 -6 ~285×10 -6 .

[0073] The content of the monovalent alkali metal ion is expressed as follows: 2 , convert the monovalent alkali metal ion into M 2 The molar ratio of O (wherein M represents a monovalent alkali metal atom) can be set to an amount corresponding to 15 ppm to 600 ppm, or 15 ppm to 500 ppm, or 15 ppm to 400 ppm.

[0074] The hollow silica sol of the present invention can be set to an average particle size measured by dynamic light scattering in the range of 20 to 150 nm. Moreover, the value of the particle size by dynamic light scattering after the hollow silica sol is stored at 50°C for 48 hours is within 2.0 times, within 1.5 times, or within 1.1 times compared to before storage. In addition, the present invention also includes that the particle size by dynamic light scattering after storage at 50°C for 48 hours is smaller than that before storage. Therefore, the lower limit can be set to 0.8 times or more, or 0.9 times or more, or 1.0 times or more.

[0075] In the present invention, the stability of the hollow silica sol can be ensured by containing sodium ions within the above range, so that the sodium ions can be contained within the above range before the sol containing the hollow silica particles becomes unstable. In addition, by adding the above sodium ions to the sol containing the unstable hollow silica particles, the agglomerated state of the hollow silica particles is released, and the particle size range of the hollow silica particles can be returned to the state before agglomeration.

[0076] In the present invention, aluminum atoms can be converted into Al by measuring the aluminum present on the surface of the silica particles by leaching the silica particles with an aqueous solution of at least one inorganic acid selected from sulfuric acid, nitric acid and hydrochloric acid. 2 O 3 That is, the mass of aluminum atoms measured by the leaching method is expressed as Al 2 O 3 After conversion, the SiO 2 The mass is 100~20000ppm / SiO 2 , or 100~15000ppm / SiO 2 , 100~10000ppm / SiO 2 , or 200~5000ppm / SiO 2 , or 500~5000ppm / SiO 2 , or 800~3000ppm / SiO 2 The ratio (A) of the above is combined with the silica particles on the surface of the hollow silica particles. The presence of aminosilicate sites on the surface of the silica particles is important for dispersion in a solvent or resin.

[0077] Aluminum atoms present on the surface of silica particles in the form of aluminosilicates are leached (dissolved) from the silica particles in a structure in which the aluminum atoms are close to aluminum salts, aluminum oxides, or aluminum hydroxides by an aqueous solution of at least one inorganic acid selected from sulfuric acid, nitric acid, and hydrochloric acid. The aluminum atoms can be measured from the solution using an ICP emission spectrometer and converted into Al 2 O 3 In particular, a method of leaching (eluting) using an aqueous nitric acid solution is used. The aqueous nitric acid solution used for leaching can be used in the range of pH 0.5 to 4.0, 0.5 to 3.0, 0.5 to 2.0 or 1.0 to 1.5, and typically an aqueous nitric acid solution with a pH of 1.0 can be used. For example, 100 mL of the above-mentioned aqueous nitric acid solution can be added to 1 g of silica, and kept at a temperature of 20 to 70°C or 40 to 60°C for 10 to 24 hours to dissolve the aluminum compound from the surface of the silica particles, which can be used as a sample for analysis.

[0078] In the present invention, the so-called silica particle surface can be defined as the area where the aluminum compound can be dissolved by the above leaching. The solvent is evaporated from the silica sol, and the silica gel dried at 250°C is ground into silica powder. 20 mL of pH 1.0 nitric acid aqueous solution is added to 0.2 g of the silica powder, and the mixture is fully shaken. After being kept in a constant temperature bath at 50°C for 17 hours, it is centrifuged and filtered. The aluminum content in the filtrate obtained by centrifugation is measured by an ICP emission spectrometer and converted to Al2 O 3 The amount of aluminum bound to the surface of silica particles (Al 2 O 3 / SiO 2 )(ppm).

[0079] Even when aluminosilicate is formed on the surface of silica particles, aluminosilicate may be formed not only on the surface but also inside the silica particles depending on the production method. 2 O 3 The mass of aluminum atoms present in the entire hollow silica particle including the surface and the interior is converted to the mass of SiO 2 The mass ratio (B) is 120 to 50,000 ppm / SiO 2 , or 500~20000ppm / SiO 2 , or 500~10000ppm / SiO 2 , or 1000~5000ppm / SiO 2 , or 1000~4000ppm / SiO 2 and combined with silica particles in such a ratio.

[0080] The above ratio (A) / ratio (B) can be set in the range of 0.001 to 1.0, or 0.01 to 1.0, or 0.1 to 1.0, or 0.3 to 1.0, or 0.4 to 1.0, and the above ratio (A) / ratio (B) is the ratio of aluminum present on the surface of the silica particles and in the entire silica particles.

[0081] The aluminum atoms present in the entire silica particles can be measured by dissolving the silica particles in a hydrofluoric acid aqueous solution and converted into Al 2 O 3 That is, the aluminum atoms present as aluminosilicate in the entire silica particle can be converted into Al by dissolving it in a hydrofluoric acid aqueous solution and measuring it from the solution using an ICP emission spectrometer. 2 O 3 , which represents the aluminum atoms present in the entire silica particles. The hydrofluoric acid aqueous solution can be any concentration that can dissolve the silica particles, for example, a 48 mass % hydrofluoric acid aqueous solution can be used. In addition, in order to completely dissolve the silica particles, the amount of the hydrofluoric acid aqueous solution used needs to be equivalent or more relative to the silica particles, preferably 1.1 to 1000 equivalents in terms of molar ratio.

[0082] In this way, by forming aluminosilicate sites on the surface of the silica particles, the negative charge amount (surface charge amount) of the hollow silica particles present on the surface of the silica particles is increased by SiO 2 The conversion can be measured within the range of 5 to 250 μeq / g, 5 to 150 μeq / g, 5 to 100 μeq / g, 25 to 150 μeq / g, or 25 to 100 μeq / g per gram.

[0083] The hollow silica particles can be obtained as hollow silica sol dispersed in a dispersion medium. The hollow silica sol dispersed in a dispersion medium can be obtained as a hollow silica sol having an average particle size of 20 to 150 nm as determined by a dynamic light scattering method.

[0084] The hollow silica is obtained by forming a shell mainly composed of silica on the surface of a portion corresponding to a core called a "template" in a dispersion medium, and then removing the portion corresponding to the core. In this state, it is a hollow silica aqueous sol.

[0085] The hollow silica aqueous sol thus obtained may be replaced by an alcohol solvent as an organic solvent. The alcohol solvent is preferably an alcohol having 1 to 5 carbon atoms with an ether bond, and examples thereof include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc. Then, after coating with a silane compound as needed, solvent replacement may be further performed with other organic solvents.

[0086] In the present invention, examples of the organic solvent include alcohols, ketones, ethers, amides, ureas and esters having 1 to 10 carbon atoms.

[0087] The alcohol having 1 to 10 carbon atoms is an aliphatic alcohol, and primary alcohol, secondary alcohol, and tertiary alcohol can be mentioned. Moreover, these alcohols can also be polyhydric alcohols, and for example, dihydric alcohols and trihydric alcohols can be mentioned.

[0088] Examples of the monovalent primary alcohol include methanol, ethanol, 1-propanol, 1-butanol, and 1-hexanol.

[0089] Examples of the monovalent secondary alcohol include 2-propanol, 2-butanol, cyclohexanol, propylene glycol monomethyl ether, and propylene glycol monoethyl ether.

[0090] Examples of the monovalent tertiary alcohol include tert-butyl alcohol and the like.

[0091] Examples of the diol include methanediol, ethylene glycol, and propylene glycol.

[0092] Examples of the trivalent alcohol include glycerin and the like.

[0093] As the ketone having 1 to 10 carbon atoms, aliphatic ketones can be preferably used, and examples thereof include acetone, methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and methylcyclopentanone.

[0094] As the ether having 1 to 10 carbon atoms, aliphatic ethers can be preferably used, and examples thereof include dimethyl ether, ethyl methyl ether, diethyl ether, tetrahydrofuran, and 1,4-dioxane.

[0095] Examples of the amide having 5 to 20 carbon atoms include N-methylpyrrolidone, dimethylacetamide, and diethylacetamide.

[0096] Examples of the urea having 5 to 20 carbon atoms include tetramethylurea and 1,3-dimethyl-2-imidazolidinone.

[0097] As the ester having 1 to 10 carbon atoms, aliphatic esters can be preferably used, and examples thereof include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl acrylate, ethyl acrylate, propyl acrylate, dimethyl maleate, diethyl maleate, dipropyl maleate, dimethyl adipate, diethyl adipate, and dipropyl adipate.

[0098] In the hollow silica aqueous sol and hollow silica organic solvent sol used as the above-mentioned raw materials, the average particle size of the hollow silica particles measured by the dynamic light scattering method (DLS method) can be in the range of 20 to 150 nm, or 30 to 150 nm, or 40 to 150 nm, or 50 to 150 nm, or 50 to 120 nm, or 50 to 100 nm.

[0099] The average primary particle size observed by transmission electron microscopy may be in the range of 20 to 150 nm, 30 to 150 nm, 40 to 150 nm, 50 to 150 nm, 50 to 120 nm, or 50 to 100 nm.

[0100] In addition, the specific surface area (C) obtained by the BET method (nitrogen adsorption method) can be set to 18 to 200 m 2 / g, or 50~160m 2 / g, or 60~160m 2 / g, or 70~160m 2 / g, or 80~150m 2 / g.

[0101] In addition, the specific surface area (D) calculated by transmission electron microscopy can be set to 18 to 136 m 2 / g, or 18~90m 2 / g, or 18~68m 2 / g, or 18~54m 2 / g, or 18-27m 2 / g, or 18~23m 2 / g.

[0102] In addition, the ratio of [specific surface area (C) measured by the BET method (nitrogen adsorption method)] / [specific surface area (D) converted by a transmission electron microscope] can be set in the range of 1.40 to 5.00, or 1.40 to 3.50, or 1.50 to 3.00, or 1.50 to 2.80. When the value of (C) / (D) is close to 1.0, it means that the silica particles are solid particles in which there is no space inside the shell of the silica particles, and when the value of (C) / (D) exceeds 1.0, it means that the silica particles are hollow particles in which there is space inside the shell of the silica particles.

[0103] Furthermore, the hollow silica particles can be produced so that the thickness of the outer shell thereof as observed by a transmission electron microscope is within the range of 3.0 to 15.0 nm, 4.0 to 12.0 nm, or 5.0 to 10.0 nm.

[0104] Furthermore, the refractive index of the hollow silica particles may be within the range of 1.20 to 1.45, 1.20 to 1.40, or 1.25 to 1.40.

[0105] In addition, the SiO 2 The concentration of the particles is 1 to 50% by mass, or 5 to 40% by mass, and typically 10 to 30% by mass.

[0106] The pH value of the above-mentioned sol can be adjusted in the range of acidity to alkalinity. The acidity is adjusted by adding an inorganic acid or an organic acid. In addition, the alkalinity is adjusted by adding an inorganic base or an organic base. As the organic base, an amine can be added for the purpose of pH adjustment and surface charge adjustment. The pH is set to a pH of 1 or more and less than 7 on the acidic side, and a pH of greater than 7 and less than 13 on the alkaline side.

[0107] The aqueous sol of hollow silica can be set to, for example, a pH range of 2.0 to 6.0 or 2.0 to 4.5 before adding the amine, and can be adjusted to, for example, a pH range of 3.0 to 10.0 or 3.0 to 9.0 by adding the amine.

[0108] In the case of an organic solvent sol, the above pH is the pH when the same mass of pure water as the organic solvent sol is mixed in a 1:1 ratio. The pH of the organic solvent can be measured when an organic solvent that can be mixed with water is used, but it is preferred to measure the pH in advance at the methanol solvent sol stage when the solvent is subsequently replaced with a hydrophobic organic solvent.

[0109] For example, in the case where the dispersion medium is a hydrophilic organic solvent such as methanol sol and propylene glycol monomethyl ether sol, the measurement can be performed on a solution obtained by mixing pure water and the sol in a mass ratio of 1:1. In the case where the dispersion medium is a hydrophobic organic solvent such as methyl ethyl ketone sol, the measurement can be performed on a solution obtained by mixing pure water, methanol and methyl ethyl ketone sol in a mass ratio of 1:1:1.

[0110] The hollow silica organic solvent sol is prepared by replacing the aqueous medium with an alcohol solvent having 1 to 5 carbon atoms, and then replacing the solvent with an organic solvent, but water may remain in the process. In the alcohol sol stage of the hollow silica, for example, 0.1 to 3.0% by mass, or 0.1 to 1.0% by mass of residual water may be contained in the sol. Moreover, in the stage of the organic solvent sol of the hollow silica (the dispersion medium is an organic solvent other than alcohol), 0.01 to 0.5% by mass of residual water may be contained.

[0111] In addition, in the hollow silica organic solvent sol, the viscosity can be set to a range of 1.0 to 10.0 mPa·s.

[0112] Amines may be added to the hollow silica sol of the present invention.

[0113] As the amine used in the present invention, a water-soluble amine having a water solubility of 80 g / L or more or 100 g / L or more can be used.

[0114] The hollow silica aqueous sol as a raw material and the hollow silica organic solvent sol obtained by solvent replacement may contain amine, or amine and ammonia. 2 , amines may be added and contained in the range of 0.001 to 10 mass %, or 0.01 to 10 mass %, or 0.1 to 10 mass %. In addition, amines, or alkaline components such as amines and ammonia may be expressed as the total nitrogen content in the hollow silica particle organic solvent sol, for example, these alkaline components may be contained in the range of 10 to 100000 ppm, or 100 to 10000 ppm, or 100 to 3000 ppm, or 100 to 2000 ppm, typically in the range of 200 to 2000 ppm.

[0115] The above-mentioned amines include aliphatic amines and aromatic amines, but aliphatic amines can be preferably used. The amine can be at least one amine selected from primary amines, secondary amines and tertiary amines having 1 to 10 carbon atoms. These amines are water-soluble and are at least one amine selected from primary amines, secondary amines and tertiary amines having 1 to 10 carbon atoms.

[0116] For example, primary amines include monomethylamine, monoethylamine, monopropylamine, monoisopropylamine, monobutylamine, monoisobutylamine, monosec-butylamine, monotert-butylamine, monomethanolamine, monoethanolamine, monopropanolamine, monoisopropanolamine, monobutanolamine, monoisobutanolamine, monosec-butanolamine, and monotert-butanolamine.

[0117] Examples of the secondary amine include dimethylamine, diethylamine, dipropylamine, diisopropylamine, N-methylethylamine, N-ethylisobutylamine, dimethanolamine, diethanolamine, dipropanolamine, diisopropanolamine, N-methanolethylamine, N-methylethanolamine, N-ethanolisobutylamine, and N-ethylisobutanolamine.

[0118] Examples of the tertiary amine include trimethylamine, triethylamine, tripropylamine, triisopropylamine, tributylamine, triisobutylamine, tri-sec-butylamine, tri-tert-butylamine, trimethanolamine, triethanolamine, tripropanolamine, triisopropanolamine, tributanolamine, triisobutanolamine, tri-sec-butanolamine, tri-tert-butanolamine, tripentylamine, 3-(dimethylamino)ethyl acrylate, 2-(dimethylamino)ethyl acrylate, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl acrylate, and 2-(diethylamino)ethyl methacrylate.

[0119] As the water solubility of the above-mentioned amine, 80 g / L or more or 100 g / L or more can be preferably used. As these amines, primary amines and secondary amines are preferred, and secondary amines are preferably used from the viewpoint of low volatility and high solubility, for example, diisopropylamine, diethanolamine, etc. can be exemplified.

[0120] In the present invention, by containing the above-mentioned amine, the surface charge of the hollow silica particles is SiO 2 In terms of conversion, the concentration per gram can be set to 5 μeq / g or more, or 25 μeq / g or more, and typically can be set within the range of 5 to 250 μeq / g, 25 to 250 μeq / g, 25 to 100 μeq / g, or 25 to 80 μeq / g.

[0121] In the present invention, the surface charge amount of the hollow silica particles can be adjusted to any surface charge amount by adjusting the type and addition amount of the above-mentioned amine.

[0122] In the present invention, the surface of the hollow silica particles may be coated with a silane compound.

[0123] As the silane compound, the coating may be performed with a hydrolyzate of at least one silane compound selected from the group consisting of the formula (1) and the formula (2).

[0124] In formula (1), R 1 are alkyl, halogenated alkyl, alkenyl, aryl, or an organic group having a polyether group, epoxy group, (meth)acryloyl group, mercapto group, amino group, urea group or cyano group, and are bonded to the silicon atom through a Si-C bond, R 2 Each of them represents an alkoxy group, an acyloxy group or a halogen group, and a represents an integer of 1 to 3.

[0125] In formula (2), R 3 are alkyl groups having 1 to 3 carbon atoms or aryl groups having 6 to 30 carbon atoms, and are bonded to the silicon atom through a Si-C bond. 4 represents an alkoxy group, an acyloxy group or a halogen group, Y represents an alkylene group, an NH group or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.

[0126] The alkyl group is an alkyl group having 1 to 18 carbon atoms, and examples thereof include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-methyl-cyclobutyl , 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl The invention also includes, but is not limited to, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl and 2-ethyl-3-methyl-cyclopropyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl and the like.

[0127] In addition, examples of the alkylene group include alkylene groups derived from the above-mentioned alkyl groups.

[0128] The aryl group is an aryl group having 6 to 30 carbon atoms, and examples thereof include phenyl, naphthyl, anthracenyl, and pyrenyl.

[0129] The alkenyl group is an alkenyl group having 2 to 10 carbon atoms, and examples thereof include vinyl, 1-propenyl, 2-propenyl, 1-methyl-1-vinyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylvinyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 1-pentenyl, 3-pentenyl, 4-pentenyl, 1-n-propylvinyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl , 3-methyl-1-butenyl, 3-methyl-2-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1-isopropylvinyl, 1,2-dimethyl-1-propenyl, 1,2-dimethyl-2-propenyl, 1-cyclopentenyl, 2-cyclopentenyl, 3-cyclopentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, 1-methyl-1-pentenyl, 1-methyl-2-pentenyl, 1-methyl-3-pentenyl, 1-methyl-4-pentenyl, 1-n-butylvinyl, 2-methyl-1-pentenyl, 2-methyl-2-pentenyl, etc., but are not limited to these.

[0130] The above-mentioned alkoxy group includes alkoxy groups having 1 to 10 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, 1-methyl-n-butoxy, 2-methyl-n-butoxy, 3-methyl-n-butoxy, 1,1-dimethyl-n-propoxy, 1,2-dimethyl-n-propoxy, 2,2-dimethyl-n-propoxy, 1-ethyl-n-propoxy, n-hexyloxy, etc., but are not limited to these.

[0131] The acyloxy group is an acyloxy group having 2 to 10 carbon atoms, and examples thereof include, but are not limited to, a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, an isopropylcarbonyloxy group, an n-butylcarbonyloxy group, an isobutylcarbonyloxy group, a sec-butylcarbonyloxy group, a tert-butylcarbonyloxy group, an n-pentylcarbonyloxy group, a 1-methyl-n-butylcarbonyloxy group, a 2-methyl-n-butylcarbonyloxy group, a 3-methyl-n-butylcarbonyloxy group, a 1,1-dimethyl-n-propylcarbonyloxy group, a 1,2-dimethyl-n-propylcarbonyloxy group, a 2,2-dimethyl-n-propylcarbonyloxy group, a 1-ethyl-n-propylcarbonyloxy group, an n-hexylcarbonyloxy group, a 1-methyl-n-pentylcarbonyloxy group, and a 2-methyl-n-pentylcarbonyloxy group.

[0132] Examples of the halogen group include fluorine, chlorine, bromine, and iodine.

[0133] As the organic group having a polyether group, there can be mentioned a polyether propyl group having an alkoxy group. 3 O)3 SiC 3 H 6 (OC 2 H 4 )nOCH 3 . n can be used in the range of 1 to 100 or 1 to 10.

[0134] Examples of the organic group having an epoxy group include a 2-(3,4-epoxycyclohexyl)ethyl group and a 3-glycidyloxypropyl group.

[0135] The (meth)acryloyl group refers to both an acryloyl group and a methacryloyl group. Examples of the organic group having a (meth)acryloyl group include a 3-methacryloyloxypropyl group and a 3-acryloyloxypropyl group.

[0136] Examples of the organic group having a mercapto group include a 3-mercaptopropyl group.

[0137] Examples of the organic group having an amino group include 2-aminoethyl, 3-aminopropyl, N-2-(aminoethyl)-3-aminopropyl, N-(1,3-dimethyl-butylidene)aminopropyl, N-phenyl-3-aminopropyl, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl.

[0138] Examples of the organic group having a ureido group include a 3-ureidopropyl group.

[0139] Examples of the organic group having a cyano group include a 3-cyanopropyl group.

[0140] The compound represented by the above formula (2) is preferably a compound capable of forming a trimethylsilyl group on the surface of the silica particles.

[0141] These compounds can be exemplified below.

[0142]

[0143] In the above formula, R 12 The alkoxy group includes, for example, a methoxy group and an ethoxy group. As the silane compound, a silane compound manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0144] The hydroxyl groups on the surface of the silica particles, for example, in the case of silica particles, react with the silanol groups and the silane compounds, and the surfaces of the silica particles are coated with the silane compounds through siloxane bonds. The reaction temperature can be carried out at a temperature ranging from 20°C to the boiling point of the dispersion medium, for example, in the range of 20°C to 100°C. The reaction time is about 0.1 to 6 hours.

[0145] The silane compound can be added to the silica sol in an amount corresponding to 0.1 silicon atoms / nm 2 ~6.0 / nm 2 The surface of the silica particles is coated with a silane compound in a coating amount of .

[0146] The hydrolysis of the above-mentioned silane compound requires water, but if it is a sol of an aqueous solvent, these aqueous solvents are used. The water remaining in the solvent when the aqueous medium is replaced with an organic solvent can be used. For example, water present in an amount of 0.01 to 1% by mass can be used. In addition, the hydrolysis can be carried out with or without a catalyst.

[0147] In the case of no catalyst, the surface of the silica particles is present as acidic sites. In the case of using a catalyst, metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases can be listed as hydrolysis catalysts. Metal chelate compounds as hydrolysis catalysts can include, for example, triethoxy·mono(acetylacetonate)titanium, triethoxy·mono(acetylacetonate)zirconium, etc. Organic acids as hydrolysis catalysts can include, for example, acetic acid, oxalic acid, etc. Inorganic acids as hydrolysis catalysts can include, for example, hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, phosphoric acid, etc. Organic bases as hydrolysis catalysts can include, for example, pyridine, pyrrole, piperazine, and quaternary ammonium salts. Inorganic bases as hydrolysis catalysts can include, for example, ammonia, sodium hydroxide, and potassium hydroxide.

[0148] The organic acid is at least one organic acid selected from dibasic aliphatic carboxylic acids, aliphatic hydroxycarboxylic acids, amino acids and chelating agents. Examples of dibasic aliphatic carboxylic acids include oxalic acid, malonic acid and succinic acid. Examples of aliphatic hydroxycarboxylic acids include glycolic acid, lactic acid, malic acid, tartaric acid and citric acid. Examples of amino acids include glycine, alanine, valine, leucine, serine and threonine. Examples of chelating agents include ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid and diethylenetriaminetetraacetic acid. Examples of organic acid salts include alkali metal salts, ammonium salts and amine salts of the above organic acids. Examples of alkali metals include sodium and potassium.

[0149] In the present invention, a film-forming composition containing the above-mentioned hollow silica organic solvent sol and an organic resin or polysiloxane can be obtained.

[0150] The organic resin or polysiloxane is selected from a thermosetting or photocurable resin and mixed to obtain a film-forming composition. In addition, the composition may contain a curing agent such as an amine curing agent, an acid anhydride curing agent, a radical generator curing agent (thermal radical generator, photo radical generator), or an acid generator curing agent (thermal acid generator or photo acid generator) to form a cured product.

[0151] Regarding this composition, a film-forming composition containing an organic resin or polysiloxane and a curing agent can be applied or filled on a substrate, and a cured product can be formed by heating, light irradiation or a combination thereof. Organic resins and polysiloxanes (curable resins) can include resins having functional groups such as epoxy groups or (meth) acryloyl groups, and isocyanate resins. For example, photocurable multifunctional acrylates can be preferably used.

[0152] Examples of the polyfunctional acrylate include polyfunctional acrylates having bifunctional, trifunctional, tetrafunctional, or higher functional groups in the molecule, such as neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0153] These multifunctional acrylates can also be described as follows.

[0154]

[0155]

[0156]

[0157] The film-forming composition of the present invention may contain a surfactant (leveling agent).

[0158] As the surfactant (leveling agent), anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants and silicone surfactants can be used. The surfactant (leveling agent) can be added in the range of 0.01 to 5 phr or 0.01 to 1 phr relative to the organic resin or polysiloxane.

[0159] Examples of the anionic surfactant used in the present invention include sodium and potassium salts of fatty acids, alkylbenzene sulfonates, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, α-sulfofatty acid esters, α-olefin sulfonates, monoalkyl phosphates, and alkane sulfonates.

[0160] For example, examples of the alkylbenzene sulfonate include sodium salts, potassium salts and lithium salts, such as sodium C10-C16 alkylbenzene sulfonate, C10-C16 alkylbenzene sulfonic acid, sodium alkylnaphthalene sulfonate and the like.

[0161] Examples of the higher alcohol sulfuric acid ester salt include sodium dodecyl sulfate (sodium lauryl sulfate) having 12 carbon atoms, triethanolamine lauryl sulfate, and triethanolammonium lauryl sulfate.

[0162] Examples of the polyoxyethylene alkyl ether sulfates include sodium polyoxyethylene styrenated phenyl ether sulfate, ammonium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyethylene decyl ether sulfate, ammonium polyoxyethylene decyl ether sulfate, sodium polyoxyethylene lauryl ether sulfate, ammonium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, and sodium polyoxyethylene oleyl cetyl ether sulfate.

[0163] As the α-olefin sulfonate, there are sodium α-olefin sulfonate and the like.

[0164] Examples of the alkanesulfonate include sodium 2-ethylhexyl sulfate and the like.

[0165] Examples of the cationic surfactant used in the present invention include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and amine salt-based agents.

[0166] The alkyltrimethylammonium salt is a quaternary ammonium salt having a chloride ion or a bromide ion as a counter ion, and examples thereof include dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, coconut trimethylammonium chloride, and alkyl (C16-18) trimethylammonium chloride.

[0167] Dialkyldimethylammonium salts have two lipophilic main chains and two methyl groups. Examples thereof include di(hydrogenated tallow)dimethylammonium chloride. Examples thereof include didecyldimethylammonium chloride, dicocoylalkyldimethylammonium chloride, dihardened tallowalkyldimethylammonium chloride, and dialkyl(C14-18)dimethylammonium chloride.

[0168] The alkyl dimethyl benzyl ammonium salt is a quaternary ammonium salt having one lipophilic main chain, two methyl groups and a benzyl group, and examples thereof include benzalkonium chloride and, for example, alkyl (C8-18) dimethyl benzyl ammonium chloride.

[0169] The amine salt-based agent is one in which the hydrogen atoms of ammonia are substituted with one or more hydrocarbon groups, and examples thereof include N-methylbishydroxyethylamine fatty acid ester hydrochloride.

[0170] Examples of the amphoteric surfactant used in the present invention include N-alkyl-β-alanine type alkylamino fatty acid salts, alkylcarboxybetaine type alkylbetaines, and N,N-dimethyldodecylamine oxide type alkylamine oxides. Examples of these include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazoline betaine, and lauryl dimethylamine oxide.

[0171] The nonionic surfactant used in the present invention is selected from polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, fatty acid alkanolamides. For example, as polyoxyethylene alkyl ether, polyoxyethylene dodecyl ether (polyoxyethylene lauryl ether), polyoxyalkylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyalkylene tridecyl ether, polyoxyethylene myristyl ether, polyoxyethylene hexadecyl ether, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene behenyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene isodecyl ether, etc. can be cited.

[0172] Examples of the polyoxyethylene alkylphenol ethers include polyoxyethylene styrenated phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene distyrenated phenyl ether, and polyoxyethylene tribenzylphenyl ether.

[0173] Examples of the alkyl glucoside include decyl glucoside and lauryl glucoside.

[0174] Examples of the polyoxyethylene fatty acid esters include polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyethylene glycol distearate, polyethylene glycol dioleate, and polypropylene glycol dioleate.

[0175] Examples of the sorbitan fatty acid esters include sorbitan monocaprylate, sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan monosesquioleate, and ethylene oxide adducts thereof.

[0176] Examples of the polyoxyethylene sorbitan fatty acid esters include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan triisostearate.

[0177] Examples of fatty acid alkanolamides include coconut oil fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0178] Further, polyoxyalkyl ethers or polyoxyalkyl glycols such as polyoxyethylene polyoxypropylene glycol and polyoxyethylene fatty acid esters, polyoxyethylene hydrogenated castor oil ether, sorbitan fatty acid ester alkyl ether, alkyl polyglucoside, sorbitan monooleate, sucrose fatty acid esters and the like can be mentioned.

[0179] Silicone surfactants can be used. Silicone surfactants are compounds having repeating units containing siloxane bonds in the main chain. Silicone surfactants can be used in a weight average molecular weight range of 500 to 50,000. They can be modified silicone surfactants, and structures in which organic groups are introduced into the side chains and / or ends of polysiloxanes can be listed. Examples of organic groups include amino groups, epoxy groups, alicyclic epoxy groups, methanol groups, mercapto groups, carboxyl groups, aliphatic ester groups, aliphatic amide groups, and polyether groups. Examples of silicone-based surfactants include those with the trade names ToroSilicon DC3PA, ToroSilicon SH7PA, and ToroSilicon.シリコーンDC11PA, トーレシリコーンSH21PA, トーレシリコーンSH28PA, トーレシリコーンSH 29PA, Torotron SH30PA, Torotron SH8400 (the above products are manufactured by Higashikata Co., Ltd.), Silwet l-77, L-7280, L-7001, L-7002, L-7200, L-7210, L-7220, L-7230, L7500, L-7600, L-7602, L-7604, L-7605, L-7622, ​​L-7657, L-8500, L- 8610 (all manufactured by Momentibu Pavfomans Materials Co., Ltd.), KP-341, KF-6001, KF-6002 (all manufactured by Shin-Etsu Silicone Co., Ltd.), BYK307, BYK323, BYK330 (all manufactured by Bick Chemie Co., Ltd.), etc. For example, as the polyether-modified silicone, trade name L-7001 (manufactured by DOWSIL Co., Ltd.) can be preferably used.

[0180] In the present invention, a film-forming composition containing the organic solvent sol and an organic resin or polysiloxane can be obtained. The film-forming composition can be formed into a film-forming composition containing hollow silica particles and an organic resin by removing the organic solvent from the organic solvent sol.

[0181] When the film-forming composition is a thermosetting film-forming composition, a thermosetting agent may be added in a range of 0.01 to 50 phr or 0.01 to 10 phr relative to the resin containing a functional group such as an epoxy group or a (meth)acryloyl group, for example, the thermosetting agent may be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents relative to the functional group such as an epoxy group or a (meth)acryloyl group. The equivalent of the thermosetting agent relative to the curable resin is expressed as an equivalent ratio of the thermosetting agent to the functional group.

[0182] The heat curing agent is preferably a phenolic resin, an amine curing agent, a polyamide resin, an imidazole, a polythiol, an acid anhydride, a thermal free radical generator, a thermal acid generator, etc. In particular, a free radical generator curing agent, an acid anhydride curing agent, and an amine curing agent are preferred.

[0183] These thermosetting agents can be used even if they are solid by dissolving them in a solvent. However, evaporation of the solvent leads to a decrease in density of the cured product or formation of pores, which in turn leads to a decrease in strength and water resistance. Therefore, the curing agent itself is preferably liquid at room temperature and pressure.

[0184] Examples of the phenolic resin include phenol novolac resin and cresol novolac resin.

[0185] Examples of the amine curing agent include piperidine, N,N-dimethylpiperazine, triethylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthanediamine, isophoronediamine, diaminodicyclohexylmethane, 1,3-diaminomethylcyclohexane, xylylenediamine, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. Among them, liquid diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthanediamine, isophoronediamine, diaminodicyclohexylmethane, 3,3′-diethyl-4,4′-diaminodiphenylmethane, diethyltoluenediamine and the like can be preferably used.

[0186] The polyamide resin is produced by condensation of a dimer acid and a polyamine and is a polyamide amine having a primary amine and a secondary amine in the molecule.

[0187] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and epoxyimidazole adducts.

[0188] Polythiol is, for example, a substance having a thiol group at the end of a polypropylene glycol chain or a substance having a thiol group at the end of a polyethylene glycol chain, and is preferably in a liquid state.

[0189] As the acid anhydride curing agent, the acid anhydride of the compound having a plurality of carboxyl groups in one molecule is preferred. As these acid anhydride curing agents, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol trimellitate, glycerol trimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethyltetrahydrophthalic anhydride, methylendomethyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, methylcyclohexene dicarboxylic anhydride, chlorobridged anhydride, etc. can be listed.

[0190] Examples of the thermal acid generator include sulfonium salts and phosphonium salts, and sulfonium salts are preferably used. For example, the following compounds can be exemplified.

[0191]

[0192] Examples of R include an alkyl group having 1 to 12 carbon atoms and an aryl group having 6 to 20 carbon atoms, and an alkyl group having 1 to 12 carbon atoms is particularly preferred.

[0193] Among them, methyltetrahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride (methylnadic anhydride), hydrogenated methylnadic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, methylhexahydrophthalic anhydride, methylhexahydrophthalic anhydride and a mixture of hexahydrophthalic anhydride are preferred, which are liquid at room temperature and pressure. The viscosity of these liquid anhydrides is about 10 mPa·s to 1000 mPa·s when measured at 25°C.

[0194] Examples of the thermal radical initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, tert-butyl hydroperoxide, cumyl hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, and benzoyl peroxide. These can be obtained from Tokyo Chemical Industry Co., Ltd.

[0195] In addition, when obtaining the above-mentioned cured product, a curing aid may be used in combination as appropriate. Examples of the curing aid include organic phosphorus compounds such as triphenylphosphine and tributylphosphine, quaternary phosphonium salts such as ethyltriphenylphosphonium bromide and diethyl methyltriphenylphosphonium phosphate, 1,8-diazabicyclo (5,4,0) undecane-7-ene, a salt of 1,8-diazabicyclo (5,4,0) undecane-7-ene and octanoic acid, zinc octanoate, and quaternary ammonium salts such as tetrabutylammonium bromide. These curing aids may be contained in a ratio of 0.001 to 0.1 parts by mass relative to 1 part by mass of the curing agent.

[0196] The composition can be obtained by mixing the resin, the curing agent and the optional curing auxiliary agent to obtain a thermosetting varnish. The mixing of these can be carried out in a reaction vessel using a stirring blade or a kneader.

[0197] The mixing is performed by a heating mixing method at a temperature of 60°C to 100°C for 0.5 to 1 hour.

[0198] The obtained curable film-forming composition is a thermosetting coating composition, for example, having an appropriate viscosity for use as a liquid sealing material. The liquid thermosetting film-forming composition can be prepared into any viscosity, and in order to be used as a transparent sealing material such as LED by casting, potting, dispenser, printing, etc., it can be partially sealed at any position. After the liquid thermosetting composition is directly installed on LED, etc. in liquid form by the above method, it is dried and cured to obtain an epoxy resin cured body.

[0199] A thermosetting film-forming composition (thermosetting coating composition) is applied onto a substrate and heated at a temperature of 80 to 200° C. to obtain a cured product.

[0200] When the film-forming composition is a photocurable resin composition, a photocuring agent (photoradical generator, photoacid generator) may be added in a range of 0.01 to 50 phr or 0.01 to 10 phr relative to the resin containing a functional group such as an epoxy group or a (meth)acryloyl group, for example, the photocuring agent (photoradical generator, photoacid generator) may be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents relative to the functional group such as an epoxy group or a (meth)acryloyl group. The equivalent of the photocuring agent relative to the curable resin is expressed as an equivalent ratio of the photocuring agent relative to the functional group.

[0201] The photoradical generator is not particularly limited as long as it is a substance that can directly or indirectly generate radicals by light irradiation.

[0202] As the photoradical generator, as the photoradical polymerization initiator, for example, imidazole compounds, diazo compounds, bisimidazole compounds, N-arylglycine compounds, organic azide compounds, titanocene compounds, aluminate compounds, organic peroxides, N-alkoxypyridinium salt compounds, and thioxanthone compounds can be listed. As the azide compound, p-azidobenzaldehyde, p-azidoacetophenone, p-azidobenzoic acid, p-azidophenylstyryl ketone, 4,4'-diazidechalcone, 4,4'-diazidediphenylsulfide, and 2,6-bis(4'-azidobenzyl)-4-methylcyclohexanone can be listed. As the diazo compound, 1-diazo-4-N,N-dimethylaminobenzene chloride and 1-diazo-4-N,N-diethylaminobenzene fluoroborate can be listed. Examples of the bisimidazole compound include 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetrakis(3,4,5-trimethoxyphenyl)1,2'-bisimidazole and 2,2'-bis(o-chlorophenyl)4,5,4',5'-tetraphenyl-1,2'-bisimidazole. Examples of the titanocene compound include dicyclopentadienyl-titanium dichloride, dicyclopentadienyl-titanium-bisphenyl, dicyclopentadienyl-titanium-bis(2,3,4,5,6-pentafluorophenyl), dicyclopentadienyl-titanium-bis(2,3,5,6-tetrafluorophenyl), dicyclopentadienyl-titanium-bis(2,4,6-trifluorophenyl), dicyclopentadienyl-titanium-bis(2,6-difluorophenyl), and dicyclopentadienyl-titanium-bis(2,3,4,5,6-pentafluorophenyl). Bis(methylcyclopentadienyl)-titanium-bis(2,4-difluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,3,4,5,6-pentafluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,3,5,6-tetrafluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,6-difluorophenyl) and dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl), etc.

[0203] Examples of the photoradical generator include 1,3-di(tert-butyldioxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-butyldioxycarbonyl)benzophenone, 3-phenyl-5-isoxazolone, 2-mercaptobenzimidazole, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone.

[0204] As these photoradical polymerization agents, they can be obtained, for example, by BASF under the trade name Irgacure TPO (the component is 2,4,6-trimethylbenzoyldiphenylphosphine oxide) (Formula (c1-1-1)), IGM RESINS under the trade name Omnirad 819 (the component is bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) (Formula (c1-1-2)), and IGM RESINS under the trade name Irgacure 184 (the component is 1-hydroxycyclohexyl phenyl ketone) (Formula (c1-1-3)).

[0205]

[0206] The photoacid generator is not particularly limited as long as it is a substance that can directly or indirectly generate an acid by light irradiation.

[0207] Specific examples of the photoacid generator include triazine compounds, acetophenone derivative compounds, disulfone compounds, diazomethane compounds, sulfonic acid derivative compounds, onium salts such as iodonium salts, sulfonium salts, phosphonium salts, and selenium salts, metallocene complexes, and iron arene complexes.

[0208] Examples of the onium salt used as the photoacid generator include iodonium salts such as diphenyliodonium chloride, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium methanesulfonate, diphenyliodonium toluenesulfonate, diphenyliodonium bromide, diphenyliodonium tetrafluoroborate, diphenyliodonium hexafluoroantimonate, diphenyliodonium hexafluoroarsenate, bis(p-tert-butylphenyl)iodonium hexafluorophosphate, bis(p-tert-butylphenyl)iodonium methanesulfonate, bis(p-tert-butylphenyl)iodonium toluenesulfonate, bis(p-tert-butylphenyl)iodonium trifluoromethanesulfonate, bis(p-tert-butylphenyl)iodonium trifluoromethanesulfonate, and bis(p-tert-butylphenyl)iodonium hexafluoroarsenate. Ionium tetrafluoroborate, bis(p-tert-butylphenyl)iodonium chloride, bis(p-chlorophenyl)iodonium chloride, bis(p-chlorophenyl)iodonium tetrafluoroborate, and bis(4-tert-butylphenyl)iodonium hexafluorophosphate and other bis(alkylphenyl)iodonium salts, alkoxycarbonylalkoxy-trialkylaryliodonium salts (for example, 4-[(1-ethoxycarbonyl-ethoxy)phenyl]-(2,4,6-trimethylphenyl)iodonium hexafluorophosphate, etc.), bis(alkoxyaryl)iodonium salts (for example, bis(alkoxyphenyl)iodonium salts such as (4-methoxyphenyl)phenyliodonium hexafluoroantimonate).

[0209] Examples of the sulfonium salt include triphenylsulfonium chloride, triphenylsulfonium bromide, tri(p-methoxyphenyl)sulfonium tetrafluoroborate, tri(p-methoxyphenyl)sulfonium hexafluorophosphonate, tri(p-ethoxyphenyl)sulfonium tetrafluoroborate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium hexafluoroantimonate, and triphenylsulfonium hexafluorophosphate; (4-phenylthienyl)diphenylsulfonium hexafluoroantimonate, (4-phenylthienyl)diphenylsulfonium hexafluorophosphate, bis[4-(diphenylsulfonium)phenyl]sulfide-bis-hexafluoroantimonate, bis[4-(diphenylsulfonium)phenyl]sulfide-bis-hexafluorophosphate, and (4-methoxyphenyl)diphenylsulfonium hexafluoroantimonate.

[0210] Examples of the phosphonium salt include triphenylphosphonium chloride, triphenylphosphonium bromide, tris(p-methoxyphenyl)phosphonium tetrafluoroborate, tris(p-methoxyphenyl)phosphonium hexafluorophosphonate, tris(p-ethoxyphenyl)phosphonium tetrafluoroborate, 4-chlorobenzenediazonium hexafluorophosphate, and benzyltriphenylphosphonium hexafluoroantimonate.

[0211] Examples thereof include selenium salts such as triphenylselenium hexafluorophosphate and metallocene complexes such as (η5 or η6-isopropylbenzene)(η5-cyclopentadienyl)iron(II) hexafluorophosphate.

[0212] In addition, the following compounds can also be used as the photoacid generator.

[0213]

[0214]

[0215]

[0216]

[0217]

[0218]

[0219]

[0220] As the photoacid generator, sulfonium salt compounds and iodonium salt compounds are preferred. Examples of their anion species include CF 3 SO 3 - , C 4 F 9 SO 3 - , C 8 F 17 SO 3 - , camphorsulfonic acid anion, toluenesulfonic acid anion, BF 4- PF 6 - , AsF 6 - and SbF 6 - etc. Anionic species such as phosphorus hexafluoride and antimony hexafluoride which exhibit strong acidity are particularly preferred.

[0221] The film-forming composition of the present invention may contain conventional additives as required. Such additives include, for example, pigments, colorants, thickeners, sensitizers, defoamers, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light stabilizers, etc.), plasticizers, dissolution promoters, fillers, antistatic agents, etc. These additives may be used alone or in combination of two or more.

[0222] Examples of a method for coating the film-forming composition of the present invention include flow coating, spin coating, spray coating, screen printing, casting, bar coating, curtain coating, roll coating, gravure coating, dipping, and slit coating.

[0223] In the present invention, the photocoating composition (film-forming composition) may be applied onto a substrate and cured by light irradiation. Alternatively, heating may be performed before or after light irradiation.

[0224] The thickness of the coating film can be selected from the range of about 0.01μm to 10mm depending on the purpose of the cured product. For example, when used for photoresist, it can be about 0.05~10μm (especially 0.1~5μm), when used for printed circuit boards, it can be about 5μm~5mm (especially 100μm~1mm), and when used for optical films, it can be about 0.1~100μm (especially 0.3~50μm).

[0225] When a clear coating is obtained, the visible light transmittance of the coating may be above 80%, or above 90%, typically 90-96%.

[0226] When using a photoacid generator, the irradiation or exposure light may be, for example, gamma rays, X-rays, ultraviolet rays, visible rays, etc., and is usually visible light or ultraviolet rays, especially ultraviolet rays. The wavelength of the light is, for example, 150 to 800 nm, preferably 150 to 600 nm, and more preferably about 150 to 400 nm. The irradiation light intensity varies depending on the thickness of the coating film, and may be, for example, 2 to 20,000 mJ / cm 2 , preferably 5 to 5000 mJ / cm 2As a light source, it can be selected according to the type of exposure light. For example, in the case of ultraviolet light, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a deuterium lamp, a halogen lamp, a laser (helium-cadmium laser, excimer laser, etc.) can be used. By such light irradiation, the above-mentioned composition undergoes a curing reaction.

[0227] When a thermal acid generator is used or a photoacid generator is used, the coating film is heated as needed after light irradiation, for example, at 60 to 350° C., preferably at about 100 to 300° C. The heating time can be selected from a range of 3 seconds or more (for example, 3 seconds to about 5 hours), for example, 5 seconds to 2 hours, preferably about 20 seconds to 30 minutes, and usually about 1 minute to 3 hours (for example, 5 minutes to 2.5 hours).

[0228] Furthermore, in the case of forming a pattern or image (for example, in the case of manufacturing a printed wiring board, etc.), the coating film formed on the substrate may be pattern-exposed, and the pattern-exposing may be performed by laser scanning or by light irradiation via a photomask. The pattern or image may be formed by developing (or dissolving) the non-irradiated area (unexposed portion) generated by such pattern-exposing with a developer.

[0229] As the developer, an alkaline aqueous solution or an organic solvent can be used.

[0230] Examples of the aqueous alkali solution include aqueous solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, potassium carbonate, and sodium carbonate; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine.

[0231] The alkaline developer is generally an aqueous solution of 10% by mass or less, preferably 0.1 to 3.0% by mass. Furthermore, alcohols or surfactants may be added to the developer, preferably 0.05 to 10 parts by mass, respectively, relative to 100 parts by mass of the developer.

[0232] Among them, a 0.1 to 2.38 mass % aqueous solution of tetramethylammonium hydroxide can be used.

[0233] In addition, as the organic solvent of the developer, a general organic solvent can be used, for example, acetone, acetonitrile, toluene, dimethylformamide, methanol, ethanol, isopropanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol butyl ether acetate, ethyl lactate, cyclohexanone, etc., and one of them or a mixture of two or more thereof can be used. In particular, propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, etc. are preferably used.

[0234] In the present invention, in order to improve the adhesion to the substrate after development, a adhesion promoter may be added. Examples of such adhesion promoters include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole; vinyltrichlorosilane; Silane, 3-chloropropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-(N-piperidyl)propyltrimethoxysilane and other silanes, benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, urea azole, thiouracil, mercaptoimidazole, mercaptopyrimidine and other heterocyclic compounds and urea or thiourea compounds such as 1,1-dimethylurea and 1,3-dimethylurea. One of the above-mentioned adhesion promoters can be used or two or more can be used in combination. The addition amount of these adhesion promoters is usually 18% by mass or less in the solid content, preferably 0.0008 to 9% by mass, and more preferably 0.04 to 9% by mass.

[0235] In the present invention, a sensitizer may also be contained. As sensitizers that can be used, anthracene, phenothiazine, perylene, thioxanthone, benzophenone thioxanthone (ベンゾフェノンチオキサントン) etc. can be listed. Furthermore, as sensitizing pigments, thiopyrylium salt pigments, merocyanidin pigments, quinoline pigments, styrylquinoline pigments, ketocoumarin pigments, thioxanthene pigments, xanthene pigments, 1,5-bis (5-oxygen-3-propylisoxazol-4-yl) pentamethoxyethanol (oxonol) pigments, cyanine pigments, rhodamine pigments, pyrylium salt pigments etc. can be exemplified. Anthracene sensitizers are particularly preferred. By using them together with cationic curing catalysts (radioactive cationic polymerization initiators), the sensitivity is dramatically improved. They also have a free radical polymerization initiation function. In a hybrid type in which the cationic curing system of the present invention is used together with a free radical curing system, the catalyst type can be simplified. As specific anthracene compounds, dibutoxyanthracene, dipropoxyanthraquinone, etc. are effective. The sensitizer is added in an amount of 0.01 to 20% by mass, preferably 0.01 to 10% by mass in the solid content.

[0236] The composition of the present invention can be photocured or thermally cured using a photoradical generator, a thermal radical generator, a photoacid generator, or a thermal acid generator. When a photoacid generator or a thermal acid generator is used, for example, a commonly used epoxy curing agent (such as an amine or anhydride) is not used or even if it is used, the content of the epoxy curing agent is very small, so the storage stability of the present composition is improved.

[0237] It is found that the above composition is suitable for photocationic polymerization. Its curing speed is higher than that of conventional liquid epoxy compounds (e.g., alicyclic epoxy compounds having cyclohexyloxy rings). Due to the fast curing speed, the amount of acid generator added can be reduced, or a weak acid acid generator can be used. The reduction of the acid generator is important for preventing metal corrosion due to residual acid active species after UV irradiation. Due to the fast curing speed, thick film curing can be performed.

[0238] Curing by UV irradiation can be applied to heat-sensitive materials (equipment).

[0239] The thermosetting material and photocuring material using the film-forming composition of the present invention have the characteristics of low dielectric constant, low dielectric loss tangent, fast hardness, high transparency, small curing shrinkage, etc., and can be used for covering or bonding electronic components, optical components (anti-reflection film), and precision mechanism components. For example, it can be used for bonding components such as lenses of mobile phones or cameras, optical elements such as light-emitting diodes (LEDs), semiconductor lasers (LDs), liquid crystal panels, biochips, lenses or prisms of cameras, magnetic components of hard disks such as personal computers, pickups of CD and DVD players (parts that take in light information reflected from the disk), cones and coils of speakers, magnets of motors, circuit substrates, electronic components, and components inside engines of automobiles, etc.

[0240] As a hard coating material for surface protection of automobile bodies, lamps or electrical products, building materials, plastics, etc., it can be applied to, for example, automobile and motorcycle bodies, lenses or reflectors of headlights, plastic lenses of glasses, mobile phones, game consoles, optical films, ID cards, etc.

[0241] Examples of ink materials for printing on metals such as aluminum, plastics, and the like include inks used for cards such as credit cards and membership cards, inks for printing on switches and keyboards of electrical products and OA equipment, and inkjet printer inks for CDs and DVDs.

[0242] Examples include technologies for curing resins to form complex three-dimensional objects in combination with three-dimensional CAD, optical modeling suitable for model making of industrial products, coating, bonding, optical waveguides, thick film resists, etc. for optical fibers.

[0243] In addition, the film-forming composition of the present invention can be suitably used as an insulating resin for electronic materials such as antireflection films, semiconductor sealing materials, adhesives for electronic materials, printed wiring board materials, interlayer insulating film materials, buffer coating agents for semiconductors, enamel insulating materials, and sealing materials for power modules, or an insulating resin used in high-voltage equipment such as generator coils, transformer coils, and gas-insulated switchgear.

[0244] The hollow silica sol of the present invention can be produced by including the following steps (I) to (II).

[0245] (I) Step: a step of preparing hollow silica sol,

[0246] Step (II): In the hollow silica sol of step (I), SiO 2 , monovalent alkali metal ions are converted to M 2 O (wherein M represents a monovalent alkali metal atom) is 7.12×10 -6 ~285×10 -6 The hollow silica sol is obtained by adjusting the ratio of the above-mentioned materials.

[0247] In the above step (II), sodium ions are preferably used as the monovalent alkali metal ions.

[0248] In the step (II), the sodium ion content can be adjusted by contacting the hollow silica sol obtained in the step (I) with a cation exchange resin or adding a sodium source. In the step (II), the sodium source is added as sodium hydroxide, preferably as an aqueous sodium hydroxide solution.

[0249] As the dispersion medium in step (I) and step (II), water, alcohol, ketone, ether, amide, urea or ester having 1 to 10 carbon atoms can be used. Examples of such dispersion medium include the above-mentioned solvents.

[0250] In the present invention, at least one step selected from the following (i) to (iv) may be added to the above step (I), step (II), or both steps.

[0251] (i): Adding amine to the hollow silica sol,

[0252] (ii): Sodium aluminate is added as an aluminum source and heated to form aluminosilicate sites in the hollow silica particles,

[0253] (iii): replacing the dispersion medium with another dispersion medium,

[0254] (iv): The hollow silica particles are coated with at least one silane compound selected from the group consisting of the compounds of formula (1) and formula (2).

[0255] The present invention also provides a method for stabilizing a hollow silica sol containing hollow silica particles having a space inside an outer shell, wherein a monovalent alkali metal ion is added to the hollow silica sol having a dynamic light scattering particle size value increased compared to the dynamic light scattering particle size at the time of production so that the monovalent alkali metal ion is converted into M 2 O (wherein M represents a monovalent alkali metal atom) relative to the SiO 2 The molar ratio becomes 7.12×10 -6 ~285×10 -6 In the above stabilization method, the monovalent alkali metal ion may be sodium ion.

[0256] Regarding the hollow silica sol in step (ii), 0.0001 to 0.5 g of an aluminum compound is added to 1 g of hollow silica particles in an aqueous sol, and the mixture is heated at 40 to 260° C. for 0.1 to 24 hours. The amount of the aluminum compound added in step (ii) may be in the range of 0.0001 to 0.5 g, 0.001 to 0.1 g, or 0.001 to 0.05 g per 1 g of hollow silica particles. Furthermore, the heating temperature in step (ii) is 40 to 260° C., 50 to 260° C., or 60 to 240° C., but in the case of non-hydrothermal treatment, the heating temperature may be 40 to 100° C., 50 to 100° C., or 60 to 100° C., and in the case of hydrothermal treatment, the heating temperature may be 100 to 260° C., or 150 to 240° C. The heating time in the step (ii) can be in the range of 0.1 to 48 hours, 0.1 to 24 hours, 0.1 to 10 hours, or 1 to 10 hours.

[0257] The hollow silica particles used in the (I) step have a shell of silica and a space inside the shell. The hollow silica is obtained by forming a shell with silica as the main component on the surface of a portion corresponding to a core called a "template" in an aqueous dispersion medium and removing the portion corresponding to the core. The template includes a method using an organic substance (for example, hydrophilic organic resin particles such as polyethylene glycol, polystyrene, and polyester) and a method using an inorganic substance (for example, hydrophilic inorganic compound particles such as calcium carbonate and sodium aluminate).

[0258] As the hollow silica aqueous sol as a raw material used in step (I), a non-hydrothermal treatment hollow silica aqueous sol can be used which has been subjected to a heating temperature below 100°C, for example, 20°C to below 100°C, or 40°C to below 100°C, or 50°C to below 100°C in an aqueous medium.

[0259] The hollow silica aqueous sol used in the step (I) may be a hydrothermally treated hollow silica aqueous sol heated to 100° C. to 240° C. or 110 to 240° C. in an aqueous medium.

[0260] The hollow silica sol used as the raw material of the present invention can be a non-hydrothermal hollow silica aqueous sol, a hydrothermal hollow silica aqueous sol or a mixture thereof. Aluminosilicate sites are formed on the outer shell of the hollow silica particles, but since the aluminosilicate sites sometimes retain alkali metals, the hollow silica sol used as the raw material can be selected based on the following conditions: the aluminum atoms measured by the leaching method are present on the surface of the hollow silica particles as Al 2 O 3 In terms of SiO 2 The mass of SiO is 100~20000ppm / SiO 2 Combine.

[0261] In step (ii), an aluminum compound is added to the hollow silica aqueous sol. The aluminum compound may be added to the hollow silica aqueous sol in the form of a solid or an aqueous solution.

[0262] The aluminum compound used in step (ii) is at least one aluminum compound selected from aluminates, alkoxyaluminums, and hydrolyzates thereof, and can be used as an aqueous solution containing them. Examples of aluminates include sodium aluminate, potassium aluminate, calcium aluminate, magnesium aluminate, ammonium aluminate, and amine aluminate. Examples of alkoxyaluminums include isopropoxyaluminum and butoxyaluminum. Aluminates are particularly preferably used.

[0263] These aluminum compounds are added to the hollow silica aqueous sol obtained in step (I) in the form of an aqueous solution, and the aluminum compound is used in a concentration range of 0.01 to 20 mass %, or 0.1 to 10 mass %, or 0.5 to 5 mass % in the aqueous solution. The addition can be performed while stirring the hollow silica aqueous sol obtained in step (I). The addition time can be completed before heating, but it can also be added during the entire heating time.

[0264] The required amount of the aluminum compound incorporated into the hollow silica particles depends on the treatment temperature in the step (ii), and the heating treatment needs to be performed within the above-mentioned temperature range.

[0265] The step (i) may further include a step of adding an amine. The amine may be added as described above, and may be contained in the hollow silica sol within the above range.

[0266] The above-mentioned step (ii) may include the following steps: adding the above-mentioned aluminum compound, or at least one additive consisting of the above-mentioned aluminum compound, an amine and a neutral salt, and then contacting with a cation exchange resin, adding an acid, or a combination of these steps. The cation exchange resin is an H-type strongly acidic cation exchange resin, and it may also be contacted with an anion exchange resin. The acid may be an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, or an organic acid such as citric acid, acetic acid, malic acid, lactic acid, succinic acid, tartaric acid, butyric acid, fumaric acid, propionic acid, formic acid, etc.

[0267] In the present invention, the step (ii) may be performed as follows: the aluminum compound (e.g., sodium aluminate) is added, and after heating at 100 to 240°C for 0.1 to 48 hours, an acid (e.g., sulfuric acid, nitric acid, hydrochloric acid) is added to contact the particles with a cation exchange resin. The addition of the acid is a leaching operation in which aluminum-containing components not doped in the particles and metal impurities contained in the particles are dissolved into the liquid by heating, and the metal-containing components are removed by a cation exchange resin. After heating and aging at 40 to 100°C for 0.1 to 48 hours, the step of contacting with a cation exchange resin may be performed again.

[0268] As step (iii), the following step may be further included:

[0269] a step of replacing the aqueous medium solvent of the aqueous sol of hollow silica with an alcohol, ketone, ether or ester having 1 to 10 carbon atoms,

[0270] Further, the step (iv) is performed of adding at least one silane compound selected from the group consisting of the formula (1) and the formula (2) and heating.

[0271] Regarding the above-mentioned steps (iii) and (iv), after the above-mentioned step (ii) is completed, the solvent in the step (iii) may be replaced with an alcohol having 1 to 10 carbon atoms, and then at least one silane compound selected from the above-mentioned formula (1) and formula (2) may be added in the step (iv), and after heating, the solvent may be further replaced with a ketone, ether, amide, urea or ester having 1 to 10 carbon atoms.

[0272] By using the above-mentioned method for producing a hollow silica sol, the surface charge of the hollow silica particles contained in the sol can be adjusted.

[0273] Example

[0274] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0275] The hollow silica sols used in Examples and Comparative Examples are as follows.

[0276] [Hollow Silica Sol]

[0277] Water-dispersed hollow silica sol (Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D, hollow silica aqueous sol, sol after heating at 100°C to 240°C in an aqueous medium, pH 9.3, dynamic light scattering particle size of 55nm, average primary particle size obtained by TEM observation: 43nm, TEM-converted specific surface area (D) 63m 2 / g, specific surface area ratio (C / D ratio) is 2.4, silicon dioxide concentration is 20% by mass, and Na content is 14 ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 6.64×10 -6 mol / SiO 2 )

[0278] [Basic compounds]

[0279] Sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd., trade name: 4 mol / L sodium hydroxide solution)

[0280] Diethanolamine (Tokyo Chemical Industry Co., Ltd., trade name: diethanolamine)

[0281] The physical properties of the water-dispersed hollow silica sol, the dispersions of silica particles prepared in Examples and Comparative Examples, and the hollow silica sol and the dispersions in the dispersion production process were measured and evaluated according to the following methods.

[0282] [Silicon dioxide (SiO 2 ) concentration determination]

[0283] The silica concentration in the water-dispersed hollow silica sol, the methanol-dispersed hollow silica sol, the hollow silica sol in the manufacturing process of the methanol-dispersed hollow silica sol, and the dispersion of surface-modified silica particles is calculated by taking these hollow silica sols or dispersions into a crucible, removing the solvent by heating, calcining at 1000°C, and measuring the remaining components after calcination.

[0284] [Measurement of pH]

[0285] The pH was measured at 25°C using a pH meter (manufactured by Toa Dirkek Co., Ltd., trade name: MM-43X).

[0286] For organic solvents that can be mixed with water arbitrarily, such as methanol sol and propylene glycol monomethyl ether sol, the measurement was carried out using a solution prepared by mixing pure water and the sol in a mass ratio of 1:1. For organic solvent sols with low solubility in water, such as methyl ethyl ketone sol, the measurement was carried out using a solution prepared by mixing pure water, methanol and its organic solvent sol in a mass ratio of 1:1:1.

[0287] [Determination of water content]

[0288] The water content of organic solvent dispersion sol was determined by Karl Fischer titration.

[0289] [Analysis method of Na content]

[0290] 0.2 g of the powder obtained by drying the hollow silica sol was treated with 20 mL of a 48 mass % hydrofluoric acid solution to remove the silicon dioxide component, and the residue was dissolved in 20 mL of a 0.1 mol / L (N / 10) nitric acid aqueous solution. The Na content in the obtained aqueous solution was measured using an ICP-OES analyzer (trade name CIROS120 E0P (Strain) Rigaku), and the Na content in the entire silica particle was obtained by dividing it by the Si content.

[0291] [Determination of particle size by dynamic light scattering (DLS)]

[0292] The dynamic light scattering particle size was measured using a dynamic light scattering particle size measuring apparatus (manufactured by Spectoris, trade name: Zetascale Nano). The Z average particle size was used as the dynamic light scattering particle size.

[0293] [Specific surface area (C) (S N 2 )]

[0294] The specific surface area (S N2 ), is obtained by removing water-soluble cations from water-dispersed hollow silica sol with a cation exchange resin (manufactured by Daw Chemical Co., Ltd., trade name: Anvarite IR-120B), drying the hollow silica sol at 290°C as a measurement sample, and measuring the specific surface area using a nitrogen adsorption method using a Monosorb specific surface area measuring apparatus (manufactured by Kantagaku Instruments Japan Corporation).

[0295] [Average primary particle size measured by TEM (transmission electron microscope)]

[0296] The silica particles in the hollow silica sol were photographed using a transmission electron microscope (manufactured by JEOL Ltd., trade name: JEM-F200), and approximately 300 randomly selected particles were binarized using an automatic image processing and analysis device (manufactured by Nileco Co., Ltd., trade name: LUZEX'AP). The projected area was measured and the diameter was calculated by converting it into a circle to obtain the average primary particle size (HEYWOOD diameter).

[0297] [TEM-converted specific surface area (D)]

[0298] Assume the true density is 2.2 g / cm 3 The average primary particle size of the spherical particles was calculated using the average primary particle size obtained by [average primary particle size measured by TEM (transmission electron microscope)] (TEM-converted specific surface area (D) = 2720 / average primary particle size).

[0299] [Measurement of the amount of aluminum (A) bound to the surface of hollow silica particles / leaching method]

[0300] The cationic components in the hollow silica sol were removed with H-type cation exchange resin, and the dried product after the solvent was removed by heat treatment was crushed in a mortar, and then treated at 250°C for 2 hours. 0.2g of the obtained powder was put into a polypropylene container (PP sampling bottle 50mL) containing 20mL of 0.1 mol / L (N / 10) nitric acid aqueous solution, and the mixture was shaken vigorously by hand. Then, an ultrasonic cleaner (ASU CLEANER ASU-10M made by Aswan) was used for 10 minutes of ultrasonic treatment to fully fuse the powder and nitric acid aqueous solution. It was placed in a 50°C constant temperature bath for 17 hours. Then, the inner solution was cooled to room temperature and loaded into a centrifugal ultrafiltration filter (Amicon Ultra-15, fractional molecular weight 10,000), and the amount of aluminum in the filtrate obtained by centrifugation was determined using an ICP emission spectrometer, and the amount of aluminum bound to the surface of the hollow silica particles was converted into Al 2 O 3 , calculate its SiO relative to hollow silica 2 Mass ratio (Al 2 O 3 (ppm) / SiO 2 ).

[0301] [Measurement of the Amount of Aluminum (B) in the Whole Hollow Silica Particles / Dissolution Method]

[0302] Precisely weigh 0.2 g of the powder obtained by drying hollow silica sol, and treat it with 20 mL of a 48% by mass hydrofluoric acid solution to remove the silica component. Dissolve the residue in 20 mL of a 0.1 mol / L (N / 10) nitric acid aqueous solution. Measure the amount of aluminum in the obtained aqueous solution using an ICP emission spectrometer, and convert the amount of aluminum present in the entire hollow silica particles into Al 2 O 3 , and calculate its ratio to the mass of SiO 2 in the hollow silica (Al 2 O 3 (ppm) / SiO 2 ).

[0303] [Measurement of the surface charge amount of hollow silica particles]

[0304] Add hollow silica sol to 10 mL of methanol and dilute it to a silica concentration of 0.5% by mass to obtain a sample for measurement. Using a particle charge meter (manufactured by Fritsch Turbo Co., Ltd., trade name: PCD-06), and using a 0.001 mol / L (N / 1000) diallyldimethylammonium chloride solution (manufactured by Fritsch Turbo Co., Ltd.) as the cation standard titrant, measure the titration value until the streaming potential of the sample for measurement becomes zero. By dividing the obtained titration value by the mass of silica contained in the sample for measurement, convert it to a value corresponding to 1 g of hollow silica particles as the surface charge amount (μeq / g-SiO 2 ).

[0305] [Example 1]

[0306] (a) Process: Charge 150 g of water-dispersed hollow silica sol (manufactured by Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) into a 500 cc eggplant-shaped flask, and while stirring with a magnetic stirrer, add an aqueous sodium hydroxide solution in such a way that the sodium content in the water-dispersed hollow silica sol is 384 ppm / SiO 2 (that is, the amount of contained Na 2 O, calculated as the molar ratio of Na 2 O to SiO 2 is 182.16×10 -6 moles / SiO 2 ). The obtained silica sol has a pH of 10.1, a particle size by dynamic light scattering method of 55 nm, an average primary particle size obtained by TEM observation of 43 nm, a silica concentration of 20% by mass, a specific surface area (C) obtained by the BET method of 150 m 2 / g, and a specific surface area (D) converted by TEM of 63 m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted to Al 2 O 3 After that, relative to the SiO 2 The mass ratio of the hollow silica sol is 0.5 ppm, the (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 384 ppm / SiO 2 , that is, the Na 2 O amount, in Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0307] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0308] The obtained methanol-dispersed hollow silica sol had a silica concentration of 21 mass %, a water content of 1.3 mass %, a particle size of 66 nm by dynamic light scattering, a pH of 9.0, and a specific surface area (C) of 150 m by BET method. 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2 O 3 After that, relative to the SiO 2 The mass is 0.1 ppm, and the amount of aluminum (B) present in the entire particle is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio is 0.5ppm, the (A / B ratio) is 0.20, and the sodium content in the methanol-dispersed hollow silica sol is 384ppm / SiO 2 , that is, the Na 2 O amount, in Na 2 O relative to SiO 2 The molar ratio is 182×10 -6mol / SiO 2 .

[0309] The obtained methanol-dispersed hollow silica sol was sealed in a 30cc glass bottle and then stored in an explosion-proof thermostatic bath (manufactured by Espec Co., Ltd., trade name: thermostatic bath with safety valve) at 50°C for 48 hours. The dynamic light scattering particle size before and after storage at 50°C was compared to confirm the stability of the methanol-dispersed hollow silica sol. Regarding the dynamic light scattering particle size before being put into 50°C, if the value of the dynamic light scattering particle size after storage at 50°C for 48 hours is within 2.0 times that before storage, it is evaluated as "stable", and if it exceeds 2.0 times, it is evaluated as "unstable". The stability of the methanol-dispersed hollow silica sol obtained in Example 1 is shown in Table 1.

[0310] [Example 2]

[0311] (a) Step: 150 g of water-dispersible hollow silica sol (Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant flask and stirred with a magnetic stirrer so that the sodium content of the water-dispersible hollow silica sol was 384 ppm / SiO 2 (i.e. Na 2 O amount, in Na 2 O relative to SiO 2 The molar ratio was calculated to be 182.16×10 -6 mol / SiO 2 ) was added dropwise with an aqueous sodium hydroxide solution. Furthermore, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The obtained silica sol had a pH of 10.2, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m by BET method. 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted to Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 384ppm / SiO 2 , that is, the Na 2 O amount, in Na 2O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0312] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0313] The obtained methanol-dispersed hollow silica sol had a silica concentration of 21 mass %, a water content of 0.4 mass %, a particle size of 66 nm by dynamic light scattering, and a specific surface area (C) of 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, the (A / B ratio) is 0.20, and the sodium content in the methanol-dispersed hollow silica sol is 384ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0314] The same stability test as in Example 1 was carried out, and the results are shown in Table 1.

[0315] [Example 3]

[0316] (a) Step: 150 g of water-dispersible hollow silica sol (Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant flask and stirred with a magnetic stirrer so that the sodium content of the water-dispersible hollow silica sol was 384 ppm / SiO 2 (i.e. Na 2 O amount, in Na 2O relative to SiO 2 The molar ratio was calculated to be 182.16×10 -6 mol / SiO 2 ) was added dropwise with an aqueous sodium hydroxide solution. Furthermore, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The pH of the silica sol obtained was 10.2, the particle size by dynamic light scattering was 55 nm, the average primary particle size obtained by TEM observation was 43 nm, the silica concentration was 20% by mass, and the specific surface area (C) obtained by the BET method was 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of the hollow silica sol is 0.5 ppm, the (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 384 ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0317] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0318] 30 g of the hollow silica sol dispersed in methanol was added to a 50 cc eggplant flask, and 0.33 g of pure water was added while stirring with a magnetic stirrer. The obtained hollow silica sol dispersed in methanol had a silica concentration of 21% by mass, a water content of 1.5% by mass, a particle size of 66 nm by the dynamic light scattering method, and a specific surface area (C) of 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, the (A / B ratio) is 0.20, and the sodium content in the methanol-dispersed hollow silica sol is 384ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0319] [Example 4]

[0320] (a) Step: 150 g of water-dispersible hollow silica sol (manufactured by Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant-shaped flask, and an aqueous sodium hydroxide solution was added dropwise while stirring with a magnetic stirrer to adjust the sodium content of the water-dispersible hollow silica sol to 192 ppm / SiO 2 (i.e. Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio was calculated to be 91.08×10 -6 mol / SiO 2 ). Then, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The pH of the silica sol obtained was 9.8, the particle size by dynamic light scattering was 55 nm, the average primary particle size obtained by TEM observation was 43 nm, the silica concentration was 20% by mass, and the specific surface area (C) obtained by the BET method was 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of the hollow silica sol is 0.5 ppm, the (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 192 ppm / SiO 2 , that is, the Na 2O amount, in Na 2 O relative to SiO 2 The molar ratio is 91×10 -6 mol / SiO 2 .

[0321] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0322] The obtained methanol-dispersed hollow silica sol had a silica concentration of 21 mass %, a water content of 0.6 mass %, a particle size of 66 nm by dynamic light scattering, and a specific surface area (C) of 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, (A / B ratio) is 0.20, and the sodium content in the methanol dispersed hollow silica sol is 192ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0323] The same stability test as in Example 1 was carried out, and the results are shown in Table 1.

[0324] [Example 5]

[0325] (a) Step: 150 g of water-dispersible hollow silica sol (manufactured by Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant-shaped flask, and an aqueous sodium hydroxide solution was added dropwise while stirring with a magnetic stirrer to adjust the sodium content of the water-dispersible hollow silica sol to 192 ppm / SiO 2 (i.e. Na2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio was calculated to be 91.08×10 -6 mol / SiO 2 ). Then, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The pH of the silica sol obtained was 9.8, the particle size by dynamic light scattering was 55 nm, the average primary particle size obtained by TEM observation was 43 nm, the silica concentration was 20% by mass, and the specific surface area (C) obtained by the BET method was 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of the hollow silica sol is 0.5 ppm, the (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 192 ppm / SiO 2 , that is, the Na 2 O amount, in Na 2 O relative to SiO 2 The molar ratio is 91×10 -6 mol / SiO 2 .

[0326] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0327] 30 g of the obtained methanol-dispersed hollow silica sol was added to a 50 cc eggplant-shaped flask, and 0.27 g of pure water was added while stirring with a magnetic stirrer. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21% by mass, a water content of 1.5% by mass, a particle size of 66 nm by the dynamic light scattering method, and a specific surface area (C) of 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, (A / B ratio) is 0.20, and the sodium content in the methanol dispersed hollow silica sol is 192ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0328] The same stability test as in Example 1 was carried out, and the results are shown in Table 1.

[0329] [Example 6]

[0330] (a) Step: 150 g of water-dispersible hollow silica sol (Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant flask, and 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The silica sol obtained had a pH of 9.5, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m by BET method. 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted into Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of the hollow silica sol is 0.5 ppm, the (A / B ratio) is 0.20, and the sodium content in the water-dispersed hollow silica sol is 14 ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 6.64×10 -6 mol / SiO2 .

[0331] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0332] Step (c): Then, an aqueous sodium hydroxide solution diluted with methanol was added dropwise to 100 g of the obtained methanol-dispersed hollow silica sol while stirring with a magnetic stirrer, so that the sodium content in the water-dispersed hollow silica sol was 384 ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio was calculated to be 182.16×10 -6 mol / SiO 2 .

[0333] The obtained methanol-dispersed hollow silica sol had a silica concentration of 20% by mass, a water content of 1.8% by mass, a particle size of 78 nm by the dynamic light scattering method, and a specific surface area (C) of 150 m 2 / g, TEM conversion specific surface area (D) is 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, and the amount of aluminum (A) bound to the particle surface is converted to Al 2 O 3 After that, relative to the SiO 2 The mass of aluminum in the particle is 0.1 ppm, and the amount of aluminum (B) present in the particle as a whole is converted into Al 2 O 3 After that, relative to the SiO 2 The mass ratio of is 0.5ppm, the (A / B ratio) is 0.20, and the sodium content in the methanol-dispersed hollow silica sol is 384ppm / SiO 2 , that is, the Na 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 182×10 -6 mol / SiO 2 .

[0334] The same stability test as in Example 1 was carried out, and the results are shown in Table 1.

[0335] (Comparative Example 1)

[0336] Step (a): 150 g of water-dispersible hollow silica sol (manufactured by Ningbo Dilato Co., Ltd., trade name: HKT-A20-40D) was placed in a 500 cc eggplant-shaped flask, and 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer.

[0337] Step (b): Then, 56 g of methanol was added to 150 g of the obtained water-dispersed hollow silica sol, and water was distilled off while supplying methanol using a rotary evaporator under heating and reduced pressure (bath temperature: 120° C., reduced pressure: 580 Torr), thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol was 2.0% by mass or less, methanol substitution was completed to obtain 150 g of methanol-dispersed hollow silica sol.

[0338] The obtained methanol-dispersed hollow silica sol had a silica concentration of 20 mass %, a water content of 0.8 mass %, and a particle size of 123 nm as measured by dynamic light scattering. 2 The amount of O is expressed as Na 2 O relative to SiO 2 The molar ratio is 6.64×10 -6 mol / SiO 2 ).

[0339] The same stability test as in Example 1 was carried out, and the results are shown in Table 1.

[0340] Table 1

[0341]

[0342] The average particle size measured by dynamic light scattering is 20 to 150 nm, which is calculated by converting the monovalent alkali metal ions into M 2 O (wherein M represents a monovalent alkali metal atom) relative to the SiO 2 The molar ratio is 7.12×10 -6 ~285×10 -6 In Examples 1 to 6, it was confirmed that the value of the particle size by dynamic light scattering after storage at 50° C. for 48 hours was within 2.0 times that before storage, indicating high stability.

[0343] On the other hand, in the comparative examples, even though the average particle size measured by the dynamic light scattering method was 20 to 150 nm, the average particle size was 20 to 150 nm when the monovalent alkali metal ions were converted into M. 2 O (wherein M represents a monovalent alkali metal atom) relative to the SiO 2 The molar ratio is less than 7.12×10 -6It was confirmed that the sol containing them in a ratio of 1.5 to 1.5 had a particle size value by dynamic light scattering after storage at 50° C. for 48 hours that was more than 2.0 times that before storage, indicating low stability.

[0344] As shown in Table 1, in Example 6, the average particle size measured by the dynamic light scattering method was 20 to 150 nm, and the monovalent alkali metal ion was converted into M 2 O (wherein M represents a monovalent alkali metal atom) relative to the SiO 2 The molar ratio is less than 7.12×10 -6 The sol is replaced with methanol and then adjusted by adding monovalent alkali metal ions. The obtained monovalent alkali metal ions are converted into M 2 O (wherein M represents a monovalent alkali metal atom) relative to the SiO 2 The molar ratio is 7.12×10 -6 ~285×10 -6 The sol having a ratio of , had a particle size value according to a dynamic light scattering method after storage at 50°C for 48 hours within 2.0 times that before storage, confirming high stability.

[0345] Industrial Availability

[0346] The present invention relates to an aqueous sol and an organic solvent sol containing highly stable hollow silica particles, and further relates to a method for improving the stability of the above sols having reduced storage stability and a method for producing the same.

Claims

1. A hollow silica sol comprising hollow silica particles having a space inside an outer shell and monovalent alkali metal ions, The molar number of the monovalent alkali metal ion converted into M2O relative to the molar number of SiO2 in the hollow silica particles is 7.12×10 -6 ~285×10 -6 The hollow silica particles and the monovalent alkali metal ions are contained in a ratio of , wherein M represents a monovalent alkali metal atom, The average particle size measured by a dynamic light scattering method after the sol was stored at 50° C. for 48 hours was within 2.0 times the average particle size measured by a dynamic light scattering method before the storage. 2 . The hollow silica sol according to claim 1 , wherein the monovalent alkali metal ions are sodium ions.

3. The hollow silica sol according to claim 1 or 2, wherein the average particle size measured by dynamic light scattering is 20 to 150 nm.

4. The hollow silica sol according to any one of claims 1 to 3, further comprising an amine, wherein the amine is present in an amount of 0.001 to 10% by mass based on SiO2 in the hollow silica particles. 5 . The hollow silica sol according to claim 4 , wherein the amine is at least one amine selected from primary amines, secondary amines and tertiary amines having 1 to 10 carbon atoms. 6 . The hollow silica sol according to claim 4 , wherein the amine is a water-soluble amine having a water solubility of 80 g / L or more.

7. The hollow silica sol according to any one of claims 1 to 6, wherein the hollow silica particles contain aluminum atoms forming aluminosilicate sites. The aluminum atoms are bonded to the surface of the hollow silica particles. The mass of the aluminum atoms relative to the mass of SiO2 in the hollow silica particles is in the range of a ratio A of 100 to 20000 ppm in terms of Al2O3. The aluminum atomic mass is a value measured by a leaching method.

8. The hollow silica sol according to claim 7, wherein an aqueous solution of at least one inorganic acid selected from sulfuric acid, nitric acid and hydrochloric acid is used in the measurement of the leaching method for leaching aluminum atoms from a compound containing aluminum atoms bonded to the surface of the hollow silica particles.

9. The hollow silica sol according to claim 7 or 8, wherein the mass of aluminum atoms present in the entire hollow silica particles is expressed as a ratio B of 120 to 50000 ppm in terms of Al2O3 relative to the mass of SiO2 in the hollow silica particles, The mass of the aluminum atoms is a value measured by dissolving the hollow silica particles in a hydrofluoric acid aqueous solution. The ratio A / the ratio B is 0.002 to 1.

0.

10. The hollow silica sol according to any one of claims 1 to 9, comprising the hollow silica particles having a ratio of [specific surface area C of silica particles obtained by a BET method, i.e., a nitrogen adsorption method] / [specific surface area D of silica particles converted by a transmission electron microscope] of 1.40 to 5.

00. 11 . The hollow silica sol according to claim 1 , wherein the hollow silica particles contain hollow silica particles having a surface charge of 5 to 250 μeq / g per 1 g in terms of SiO 2 .

12. The hollow silica sol according to any one of claims 1 to 11, wherein the hollow silica particles further comprise hollow silica particles coated with at least one silane compound selected from the group consisting of the compound represented by the following formula (1) and the compound represented by the following formula (2), R 1 a Si(R 2 ) 4-a formula(1) 〔R R b Si(R 4 ) 3-b 〕2Y c Formula (2) In formula (1), R 1 is a group bonded to a silicon atom, and independently represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, a polyether group, a carboxyl group, a protected carboxyl group, a carboxyl generating group, an imide group or a cyano group and bonded to a silicon atom via a Si-C bond, or represents a combination of these groups, R 2 is a group or atom bonded to a silicon atom, and each independently represents an alkoxy group, an acyloxy group, a hydroxyl group or a halogen atom having 1 or more carbon atoms, or represents a combination of these groups, a represents an integer from 1 to 3, In formula (2), R 3 is a group bonded to a silicon atom, and independently represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, a polyether group, a carboxyl group, a protected carboxyl group, a carboxyl generating group, an imide group, or a cyano group and bonded to a silicon atom via a Si-C bond, or represents a combination of these groups, R 4 is a group or atom bonded to a silicon atom, and each independently represents an alkoxy group, an acyloxy group, a hydroxyl group or a halogen atom having 1 or more carbon atoms, or represents a combination of these groups, Y is a group or atom bonded to a silicon atom and represents an alkylene group, an NH group or an oxygen atom, b represents an integer of 1 to 3, and c represents an integer of 0 or 1.

13. The hollow silica sol according to any one of claims 1 to 12, wherein the dispersion medium is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea or an ester. 14 . A film-forming composition comprising hollow silica particles derived from the hollow silica sol according to claim 1 , and an organic resin or polysiloxane. 15 . A film obtained from the film-forming composition according to claim 14 , wherein the film has a visible light transmittance of 80% or more.

16. The method for producing a hollow silica sol according to any one of claims 1 to 13, comprising the following steps (I) to (II): (I) Step: a step of preparing a hollow silica sol containing a dispersion medium, Step (II): Add monovalent alkali metal ions to the hollow silica sol of step (I), and adjust the molar ratio of the monovalent alkali metal ions converted to M2O to the molar ratio of SiO2 in the hollow silica particles to 7.12×10 -6 ~285×10 -6 wherein M represents a monovalent alkali metal atom. 17 . The method for producing a hollow silica sol according to claim 16 , wherein in the step (II), the monovalent alkali metal ions are sodium ions.

18. The method for producing a hollow silica sol according to claim 17, wherein the sodium ion content is adjusted in the step (II) by contacting the hollow silica sol obtained in the step (I) with a cation exchange resin or by adding a sodium source.

19. The method for producing a hollow silica sol according to claim 17, wherein in the step (II), the addition of the sodium source is the addition of sodium hydroxide. 20 . The method for producing a hollow silica sol according to claim 16 , wherein the dispersion medium in the step (I) and the step (II) is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea or an ester.

21. The method for producing a hollow silica sol according to any one of claims 16 to 20, wherein at least one step selected from the following (i) to (iv) is added to the step (I), the step (II), or both steps. (i): Adding amine to the hollow silica sol, (ii): sodium aluminate is added as an aluminum source and heated to form aluminosilicate sites in the hollow silica particles, (iii): replacing the dispersion medium with another dispersion medium, (iv): The hollow silica particles are further coated with at least one silane compound selected from the group consisting of formula (1) and formula (2).

22. The method for stabilizing hollow silica sol according to claim 1, which is a method for stabilizing hollow silica sol comprising hollow silica particles having a space inside an outer shell, characterized in that: The monovalent alkali metal ion is added to the hollow silica sol whose average particle size value measured by the dynamic light scattering method is larger than that during production, so that the molar number of the monovalent alkali metal ion converted into M2O relative to the molar number of SiO2 of the hollow silica particles in the hollow silica sol becomes 7.12×10 -6 ~285×10 -6 The molar ratio of , wherein M represents a monovalent alkali metal atom, reduces the increased average particle size measured by dynamic light scattering. 23 . The method for stabilizing hollow silica sol according to claim 22 , wherein the monovalent alkali metal ions are sodium ions.

Citation Information

Patent Citations

  • Silica-based fine particles, coating for forming coating film, and base material having coating film formed thereon

    JP2013121911A

  • Method for producing silica sol having elongated particle shape

    CN111788153A

  • Particles having hollows inside shell, method for producing same, coating liquid containing same, and substrate with transparent coating film containing same

    CN112573526A

  • Aluminum-containing silica sol dispersed in nitrogen-containing solvent, and resin composition

    CN114746366A

  • Hollow silica particles and method for producing hollow silica particles

    CN115210179A